Casting of recycled aluminum scrap

The method of adding alloy elements to recycled aluminum for metal casting addresses the challenges of impurities and unbalanced alloying elements, enhancing the mechanical properties of metal products and promoting the efficient use of recycled materials.

JP7653393B2Active Publication Date: 2025-03-28NOVELIS INC(US)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022128289
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-03-23
Filing Date
2022-08-10
Publication Date
2025-03-28
Estimated Expiration
2038-03-23

AI Technical Summary

Technical Problem

Current metal casting techniques using recycled aluminum scraps, such as used beverage cans, face challenges due to impurities and unbalanced alloying elements, which can lead to properties like strength and formability issues, and even high temperature cracking during the casting process.

Method used

A method involving melting recycled aluminum, adding alloy elements like magnesium, silicon, or copper to form a modified liquid metal, and then casting and rolling the metal product to achieve desired mechanical properties, while maintaining at least 50% recycled aluminum content.

Benefits of technology

This method effectively improves the metallurgical and mechanical properties of metal products, such as yield strength, ultimate tensile strength, and elongation, while minimizing the need for primary aluminum and reducing processing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653393000005
    Figure 0007653393000005
  • Figure 0007653393000006
    Figure 0007653393000006
  • Figure 0007653393000007
    Figure 0007653393000007
Patent Text Reader

Abstract

To provide a method for casting a high-strength, highly formable metal product from recycled metal scrap, and to provide the cast metal product. [Solution] A metal casting method comprising: melting recycled aluminum into a liquid metal; adding alloying elements to the liquid metal to form a modified liquid metal, wherein the alloying elements comprise magnesium, silicon, or copper; casting the modified liquid metal into a metal product, wherein the modified liquid metal comprises at least 50% recycled aluminum; and rolling the metal product.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 62 / 475,489, filed March 23, 2017, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The present disclosure relates generally to metal casting, and more specifically to improvements in aluminum casting using recycled scrap, such as used beverage can scrap. [Background technology]

[0003] Recycled scrap metal includes metal from used metal products that are collected and used to prepare other metal products. For example, used beverage can (UBC) scrap is recovered from used beverage cans and similar products that can be recycled for use in further metal products. Aluminum UBC scrap is often a mixture of various aluminum alloys (e.g., from different alloys used in can bodies and can ends) and often may contain foreign materials such as rainwater, beverage residues, organic matter (e.g., paints and laminate films), and other materials. The UBC scrap may be shredded, stripped, or delacquered before being melted for use as liquid metal feedstock in casting new metal products. Due to the presence of impurities and unbalanced alloying elements in the liquid UBC metal, it is necessary to process the liquid UBC metal to remove undesirable elements or combine the liquid UBC metal with a sufficient amount of new primary aluminum before casting. Similarly, recycled scrap from other sources may have a relatively large amount of impurities and / or unbalanced alloying elements.

[0004] The presence of sufficient trace elements in the liquid metal used to cast metal products (e.g., metal strip) can adversely affect the properties of the metal products, such as strength and formability. Furthermore, impurities and elements present in UBC scrap and similar recycled scrap can cause failures and even dangerous outcomes during the casting process, such as crack formation during solidification and / or subsequent cooling of the metal product. Crack formation during these stages can render the cast product unusable and, in some cases, cause damage to people and properties.

[0005] In addition to hot cracking, concerns when using alloys with high recycled content include variations in iron, manganese, and silicon content. These elements are extremely difficult to remove, so their presence is primarily limited to prevent or reduce contamination of the scrap stream. Modification of these constituents is generally avoided, as it can modify the size and type of intermetallic phases, which translates into deviations in certain mechanical behaviors.

[0006] Thus, current techniques for using recycled scrap, such as UBC scrap, to produce certain metal products, particularly products that must have material properties within certain specification limits, are either expensive in terms of time, space, and energy (e.g., removing impurities from the liquid UBC metal or extensive post-casting processing and treatment) or require the use of significant amounts of virgin material (e.g., by diluting the liquid UBC metal with a sufficient amount of virgin metal). Summary of the Invention

[0007] The term "embodiments" and similar terms are intended to broadly refer to all of the subject matter of the present disclosure and the following claims. Statements containing these terms should be understood to neither limit the subject matter described herein nor limit the meaning or scope of the following claims. The embodiments of the present disclosure covered herein are defined by the following claims, not this Summary. This Summary is a broad overview of various aspects of the present disclosure and introduces some of the concepts that are further described in the "Detailed Description" section below. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to appropriate portions of the entire specification of this disclosure, any or all drawings, and each claim.

[0008] Described herein is a metal casting method that includes melting recycled aluminum into a liquid metal, adding an alloying element to the liquid metal to form a modified liquid metal, the alloying element including magnesium, silicon, or copper, casting the modified liquid metal into a metal product, the modified liquid metal including at least 50% recycled aluminum, and rolling the metal product. Optionally, rolling includes hot rolling the metal product to a gauge for delivery, cold rolling the metal product to a gauge for delivery, or hot rolling and cold rolling the metal product for delivery. The gauge for delivery can be an intermediate gauge or a final gauge. The modified liquid metal can include magnesium in an amount up to about 7% by weight. In some cases, the modified liquid metal includes magnesium in an amount of at least 1.5% by weight (e.g., about 1.5% to about 7% by weight or about 1.5% to about 4% by weight). The method may further include reheating the metal product after rolling to an annealing temperature, the annealing temperature being below the solidus temperature of the metal product. Optionally, the casting may include continuously casting the modified liquid metal or directly chill casting the modified liquid metal. The recycled aluminum may include used beverage can scrap containing a mixture of recycled metals from can ends and can bodies. In some cases, the modified liquid metal includes at least about 60% recycled aluminum (e.g., at least about 80% recycled aluminum). Optionally, the modified liquid metal may include a hydrogen content of 0.25 mL / 100 grams or less. Also described herein are metal products cast from recycled materials according to the methods described herein.

[0009] There is further provided herein a metal product comprising an aluminum alloy comprising approximately 0.01 wt%-1.0 wt% Cu, 0.15 wt%-0.8 wt% Fe, 0.5 wt%-7.0 wt% Mg, 0.01 wt%-1.2 wt% Mn, up to 1.5 wt% Si, up to 0.15 wt% impurities, and Al, wherein the metal product is cast from a modified liquid metal comprising at least 50% recycled aluminum. Optionally, the aluminum alloy includes about 0.1-0.9 wt.% Cu, 0.25-0.7 wt.% Fe, 1.0-5.0 wt.% Mg, 0.1-0.9 wt.% Mn, 0.01-1.0 wt.% Si, 0.01-0.15 wt.% Ti, 0.01-5.0 wt.% Zn, 0.01-0.25 wt.% Cr, 0.01-0.1 wt.% Zr, up to 0.15 wt.% impurities, and Al. Optionally, the aluminum alloy comprises about 0.2-0.8 wt% Cu, 0.3-0.6 wt% Fe, 1.4-3.0 wt% Mg, 0.2-0.7 wt% Mn, 0.2-0.5 wt% Si, 0.02-0.1 wt% Ti, 0.02-3.0 wt% Zn, 0.02-0.1 wt% Cr, 0.02-0.05 wt% Zr, up to 0.15 wt% impurities, and Al. In some cases, the modified liquid metal comprises at least about 60% recycled aluminum (e.g., at least about 80% recycled aluminum). Optionally, the modified liquid metal can comprise a hydrogen content of 0.25 mL / 100 grams or less. The recycled aluminum can comprise used beverage can scrap, including a mixture of recycled metals from can ends and can bodies. In some cases, the metal product comprises a yield strength of at least 100 MPa, an ultimate tensile strength of at least 210 MPa, a uniform elongation of at least 18%, and / or a total elongation of at least 20.5%. The metal product may comprise an Fe-containing component. Optionally, the Fe-containing component has a length in the range of about 0.6 μm to about 1.8 μm. In some cases, the metal product comprises intermetallic particles having a width-to-height ratio of about 3 or less. [Brief description of the drawings]

[0010] This specification refers to the following accompanying drawings, in which the use of like reference numbers in different drawings is intended to illustrate the same or similar elements.

[0011] [Figure 1] 1 is a flow chart illustrating a process for casting and hot rolling UBC or other scrap-derived metal products according to certain embodiments of the present disclosure. [Diagram 2] 1 is a flow chart illustrating a process for casting and cold rolling UBC or other scrap-derived metal products according to certain embodiments of the present disclosure. [Diagram 3] FIG. 1 is a flow chart illustrating a process for casting and rolling UBC or other scrap-derived metal products using hot and cold rolling, according to certain embodiments of the present disclosure. [Figure 4] FIG. 1 is a schematic diagram illustrating a separate metal casting and rolling system in accordance with certain aspects of the present disclosure. [Diagram 5] FIG. 1 is a schematic diagram illustrating a continuous casting system according to certain aspects of the present disclosure. [Figure 6] 1 is a chart illustrating longitudinal and transverse elongation and strength of metal products formed according to certain aspects of the present disclosure. [Figure 7] 1 is a chart showing the yield strength of metal product samples prepared using a UBC-based alloy having 1.5 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 8] 8 is a chart 800 illustrating the ultimate tensile strength of metal product samples prepared using a UBC-based alloy having 1.5 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 9] 1 is a chart showing uniform elongation of metal product samples prepared using a UBC-based alloy having 1.5 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 10]1 is a chart showing the total elongation of metal product samples prepared using a UBC-based alloy having 1.5 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 11] 1 is a chart showing three-point bend test results (internal bend angle β) of metal product samples prepared using a UBC-based alloy having 1.5 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 12] 1 is a chart showing plastic deformation test results of metal product samples prepared using a UBC series alloy having 1.5 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 13] 1 is a series of photomicrographs of metal product samples prepared using a UBC-based alloy having 1.5 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 14] 1 is a chart showing the yield strength of metal product samples prepared using a UBC-based alloy having 2.59 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 15] 1 is a chart showing the ultimate tensile strength of metal product samples prepared using a UBC-based alloy having 2.59 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 16] 1 is a chart showing uniform elongation of metal product samples prepared using a UBC-based alloy having 2.59 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 17] 1 is a chart showing the total elongation of metal product samples prepared using a UBC-based alloy having 2.59 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 18] 1 is a chart showing three-point bend test results (internal bend angle β) of metal product samples prepared using a UBC-based alloy having 2.59 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 19] 1 is a chart showing plastic deformation test results of metal product samples prepared using a UBC series alloy having 2.59 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 20]1 is a series of photomicrographs of metal product samples prepared using a UBC-based alloy having 2.59 wt. % Mg, according to certain embodiments of the present disclosure. [Figure 21] 1 is a series of flow charts illustrating a process for preparing and manufacturing a UBC-based aluminum alloy, according to certain embodiments of the present disclosure. [Figure 22] 1 is a chart showing yield strength, ultimate tensile strength, uniform elongation, and total elongation of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 23] 1 is a chart showing the texture component content of metal product samples prepared using UBC-based alloys, according to certain embodiments of the present disclosure. [Figure 24] 1 is a chart showing yield strength of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 25] 1 is a chart showing the ultimate tensile strength of metal product samples prepared using UBC-based alloys, according to certain embodiments of the present disclosure. [Figure 26] 1 is a chart showing uniform elongation of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 27] 1 is a chart showing the total elongation of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 28] 1 is a chart showing three-point bend test results (outer bend angle α) of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 29] FIG. 1 is a schematic diagram illustrating a three-point bend test method including an inner bend angle β and an outer bend angle α according to certain embodiments of the present disclosure. [Diagram 30] 1 is a chart showing yield strength of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 31]1 is a chart showing the ultimate tensile strength of metal product samples prepared using UBC-based alloys, according to certain embodiments of the present disclosure. [Diagram 32] 1 is a chart showing uniform elongation of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 33] 1 is a chart showing the total elongation of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 34] 1 is a chart showing three-point bend test results (outer bend angle α) of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 35] 1 is a chart showing yield strength of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 36] 1 is a chart showing the ultimate tensile strength of metal product samples prepared using UBC-based alloys, according to certain embodiments of the present disclosure. [Figure 37] 1 is a chart showing uniform elongation of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 38] 1 is a chart showing the total elongation of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 39] 1 is a chart showing three-point bend test results (outer bend angle α) of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 40] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 41] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 42] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 43] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 44] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 45] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 46] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 47] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 48] 1 is a chart showing the texture component content of metal product samples prepared using UBC-based alloys, according to certain embodiments of the present disclosure. [Figure 49] 1 is a chart showing the texture component content of metal product samples prepared using UBC-based alloys, according to certain embodiments of the present disclosure. [Figure 50] 1 is a chart showing the texture component content of metal product samples prepared using UBC-based alloys, according to certain embodiments of the present disclosure. [Figure 51] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 52] 1 is a series of photomicrographs of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Diagram 53] 1 is a chart showing particle size distribution of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 54]1 is a chart showing grain aspect ratios of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 55] 1 is a chart showing stress-strain curves of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 56] 1 is a chart showing stress-strain curves of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. [Figure 57] 1 is a chart showing stress-strain curves of metal product samples prepared using UBC-based alloys according to certain embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Certain aspects and features of the present disclosure relate to improvements in casting metal products from recycled scrap metal (e.g., recycled aluminum scrap, such as used beverage can (UBC) scrap). The recycled scrap metal can be used to prepare metal products having suitable mechanical properties (e.g., strength and formability) for use in various applications, such as automotive applications (e.g., hood inners) and household items (e.g., cookware, including pots and pans). The addition of certain desirable trace elements to the liquid metal prepared from the recycled scrap can result in a modified liquid metal. The modified liquid metal can be used to prepare recycled content alloys. The recycled content alloys can be cast, for example, using direct chill casting or continuous casting. For example, using recycled content alloys in a continuous casting process can result in cast alloy products with minimal risk of hot cracking during the casting process. In some cases, a combination of casting and subsequent hot rolling processes to final gauge can produce desired metal coils of final gauge with desirable mechanical properties. The concepts disclosed herein allow inexpensive and recycled scrap metal to be efficiently reused for new applications, such as certain automotive parts or replacement can bodies. For example, metal products cast and rolled as disclosed herein can meet and / or exceed the specification requirements set by original equipment manufacturers (OEMs) for automotive hoods, deck lids, or inner door panels. While certain embodiments of the present disclosure may be used with any suitable metal as desired, certain embodiments of the present disclosure are particularly well suited for use with aluminum.

[0013] Definitions and Explanations: The terms "invention," "the invention," "this invention," and "the present invention" as used herein are intended to refer broadly to all of the subject matter of this patent application and the claims that follow. Statements containing these terms are to be understood as not limiting the subject matter described herein or the meaning or scope of the claims that follow.

[0014] As used herein, the meanings of "a," "an," or "the" include singular and plural references unless the context clearly dictates otherwise.

[0015] As used herein, plate generally has a thickness of greater than about 15 mm. For example, plate may refer to an aluminum product having a thickness of greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, or greater than about 100 mm.

[0016] As used herein, a shade (also referred to as a sheet plate) generally has a thickness of about 4 mm to about 15 mm. For example, the shade may have a thickness of about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm, or about 15 mm.

[0017] As used herein, sheet generally refers to an aluminum product having a thickness of less than about 4 mm. For example, the sheet may have a thickness of less than about 4 mm, less than about 3 mm, less than about 2 mm, less than about 1 mm, less than about 0.5 mm, or less than about 0.3 mm (e.g., about 0.2 mm).

[0018] As used herein, the term foil refers to an alloy thickness in the range of up to about 0.2 mm (i.e., 200 microns (μm)). For example, the foil may have a thickness of up to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, or 200 μm.

[0019] In this description, reference is made to alloys identified by aluminum industry designations such as "series" or "5xxx." For an understanding of the number designation systems most commonly used in naming and identifying aluminum and its alloys, reference is made to "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Compositions Limits for Aluminum Alloys in the Form of Castings and Ingot," both published by The Aluminum Association.

[0020] In this application, alloy tempers or conditions are referred to. For an understanding of the descriptions of the most commonly used alloy tempers, please refer to "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". The F condition or temper refers to the aluminum alloy as produced. The O state or temper refers to the aluminum alloy after annealing. The Hxx state or temper, also referred to herein as the H temper, refers to the non-heat treatable aluminum alloy after cold rolling with or without heat treatment (e.g., annealing). Suitable H tempers include the HX1, HX2, HX3, HX4, HX5, HX6, HX7, HX8, or HX9 tempers. The T1 state or temper refers to the aluminum alloy that has been cooled from hot working and naturally aged (e.g., at room temperature). The T2 state or temper refers to the aluminum alloy that has been cooled from hot working, cold worked, and naturally aged. The T3 state or temper refers to the aluminum alloy solution that has been heat treated, cold worked, and naturally aged. The T4 state or temper refers to the aluminum alloy solution that has been heat treated, and naturally aged. The T5 state or temper refers to the aluminum alloy solution that has been cooled from hot working and artificially aged (at high temperature). The T6 state or temper refers to the aluminum alloy solution that has been heat treated, and artificially aged. The T7 state or temper refers to the aluminum alloy solution that has been heat treated, and artificially aged. The T8x state or temper refers to the aluminum alloy solution that has been heat treated, cold worked, and artificially aged. The T9 state or temper refers to the aluminum alloy solution that has been heat treated, artificially aged, and cold worked. The W state or temper refers to the aluminum alloy after a solution heat treatment.

[0021] As used herein, the meaning of "room temperature" can include temperatures from about 15°C to about 30°C, such as about 15°C, about 16°C, about 17°C, about 18°C, about 19°C, about 20°C, about 21°C, about 22°C, about 23°C, about 24°C, about 25°C, about 26°C, about 27°C, about 28°C, about 29°C, or about 30°C.

[0022] As used herein, the terms "cast metal product," "cast product," "cast aluminum alloy product," and the like are used interchangeably and refer to products produced by direct chill casting (including direct chill co-casting) or semi-continuous casting, continuous casting (including, for example, using a twin belt caster, twin roll caster, block caster, or any other continuous casting machine), electromagnetic casting, hot top casting, or any other casting method.

[0023] As used herein, the term metal product may refer to any suitable shape or size of cast product, as appropriate.

[0024] All ranges disclosed herein are understood to encompass any and all subranges subsumed therein. For example, a stated range of "1 to 10" should be considered to include any and all subranges between a minimum value of 1 and a maximum value of 10, i.e., all subranges beginning with a minimum value of 1 or greater, e.g., 1 to 6.1, and all subranges ending with a maximum value of 10 or less, e.g., 5.5 to 10.

[0025] The following aluminum alloys are listed with respect to their elemental composition in weight percentages (wt.%) based on the total weight of the alloy, with the balance being aluminum and the maximum wt.% of the sum of the impurities being 0.15 wt.% in each particular example alloy.

[0026] As used herein, the term recycled scrap (e.g., recycled feedstock) may refer to a collection of recycled metals. Recycled scrap may include recycled materials from any suitable source, such as recycled materials from metal manufacturing facilities (e.g., metal casting facilities, etc.), recycled materials from metal processing facilities (e.g., manufacturing facilities that use metal products to make consumables), or recycled materials from post-consumer sources (e.g., local recycling facilities). Certain aspects of the present disclosure may be suitable for recycled scrap from sources other than metal manufacturing facilities, possibly because such recycled scrap contains mixtures of alloys or is mixed with other impurities or elements (e.g., paints or coatings, etc.). Recycled scrap refers to recycled aluminum, such as recycled sheet aluminum products (e.g., aluminum pots and pans), recycled cast aluminum products (e.g., aluminum grills and wheel rims, etc.), UBC scrap (e.g., beverage cans), aluminum wire, and other aluminum materials.

[0027] Recycled Inclusion Alloys Described herein is a recycled inclusion alloy prepared from at least a portion of recycled scrap. For example, the techniques disclosed herein can produce suitable cast products from modified liquid metals containing about 50%, about 60%, about 70%, about 80%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, or about 99% or more recycled scrap. In other words, the cast products described herein may contain about 50%, about 40%, about 30%, about 20%, about 15%, about 10%, about 9%, about 8%, about 7%, about 6%, about 5%, about 4%, about 3%, about 2%, or about 1% or less of primary aluminum. Certain aspects of the present disclosure relate to metal products made using modified liquid metals that are mostly recycled scrap.

[0028] In some cases, recycled scrap includes recycled aluminum scrap, such as UBC scrap. For example, UBC scrap generally contains a mixture of metals from various alloys, such as metals from can bodies (e.g., 3104, 3004, or other 3xxx aluminum alloys) and can ends (e.g., 5182 or other 5xxx aluminum alloys). Other recycled scrap includes other alloy mixtures. These alloy mixtures, when melted, result in alloy compositions that may be difficult to cast as is, and the mechanical properties of the resulting product may be undesirable. Additionally, recycled scrap may contain other impurities and alloying elements, which, when melted, become liquid metal. High concentrations of impurities and alloying elements in the liquid metal may cause casting problems, such as hot cracking, elemental control problems (especially for iron, manganese, and silicon), centerline segregation, and other problems. The concentrations of these impurities and alloying elements can be reduced by treating the liquid metal (e.g., thermally, chemically, magnetically, and / or electrically) to remove the impurities or alloying elements and / or by adding fresh primary aluminum to the melt. Processing the liquid metal requires time, equipment, and energy. Because primary aluminum is more expensive to produce than recycled scrap, adding primary aluminum reduces the recycled content and increases costs. Thus, there is often a trade-off between processing recycled scrap and adding primary aluminum. Using the technology described herein, recycled scrap can be used with little or no refining and little or no addition of primary aluminum.

[0029] Optionally, the recycled scrap can be modified with one or more additional elements to prepare the recycled inclusion alloy. In some examples, it may be desirable to add magnesium (Mg) and / or other alloying elements to the recycled scrap to improve liquid metal castability and result in a recycled inclusion alloy with improved metallurgical properties of the final product. For example, adding Mg can increase the formability and strength of cast metal products. In some examples, Mg can be added to the recycled scrap to achieve a Mg percentage in the recycled inclusion alloy of about 0.50% to about 7.0% based on the total weight of the alloy (e.g., about 1.5% to about 6.0%, about 2.0% to about 5.0%, about 2.5% to about 4.5%, or about 3.0% to about 4.0%). The Mg percentages are approximately 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, and or may be greater than 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, or 7.0%. In some cases, Mg can be added to the recycled scrap to achieve a Mg percentage of at least 1.5% and about 6.0%, 5.9%, 5.8%, 5.7%, 5.6%, 5.5%, 5.4%, 5.3%, 5.2%, 5.1%, 5.0%, 4.9%, 4.8%, 4.7%, 4.6%, 4.5%, 4.4%, 4.3%, 4.2%, 4.1%, 4.0%, 3.9%, 3.8%, 3.7%, 3.6%, 3.5%, 3.4%, 3.3%, 3.2%, 3.1%, or 3.0% or less by weight in the recycled inclusion alloy.

[0030] Typically, recycled scrap, such as UBC scrap, already contains significant amounts of alloying elements, so adding additional alloying elements to the recycled scrap may not be desirable. Furthermore, the addition of alloying elements may increase the risk of hot cracking and the resulting cast product may exhibit undesirable mechanical properties. However, the addition of Mg as disclosed herein, in some cases in combination with certain processing steps detailed herein, has been found to produce surprisingly effective results. In some cases, additional copper (Cu) and / or silicon (Si) may be added to the recycled scrap prior to casting. In some cases, other alloying elements may be added to the recycled scrap prior to casting.

[0031] In some examples, the recycled inclusion alloys described herein can have the following elemental compositions shown in Table 1. [Table 1]

[0032] In some examples, the recycled inclusion alloys described herein can have the following elemental compositions shown in Table 2. [Table 2]

[0033] In some examples, the recycled inclusion alloys described herein can have the following elemental compositions shown in Table 3. [Table 3]

[0034] In some examples, the alloys described herein include Cu in an amount between about 0.01% and about 1.0% (e.g., between about 0.05% and about 1.0%, between about 0.1% and about 0.9%, between about 0.2% and about 0.8%, between about 0.15% and about 0.40%, or between about 0.20% and about 0.35%) based on the total weight of the alloy. For example, alloys may be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 5%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 10 ... 1%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0. May contain 77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, or 1.0% Cu. All percentages are by weight.

[0035] In some examples, the alloys described herein include iron (Fe) in an amount between about 0.15% and about 0.8% (e.g., between about 0.25% and about 0.7%, or between about 0.3% and about 0.6%) based on the total weight of the alloy. For example, alloys may be 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0. The material may contain 48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80% Fe. All values ​​are by weight.

[0036] In some examples, the alloys described herein include Mg in an amount between about 0.50% and about 7.0% (e.g., between about 1.0% and about 5.0%, between about 1.4% and about 3.0%, between about 1.5% and about 2.6%, or between about 1.6% and about 2.5%) based on the total weight of the alloy. For example, the alloys may include 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 10 ... 5%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.0%, 1.1% ,1.2%,1.3%,1.4%,1.5%,1.6%,1.7%,1.8%,1.9%,2.0%,2.1%,0.2%,2.3%,2.4%,2.5%,2.6%,2.7%,2.8%,2.9%,3.0%,3.1%,3.2%,3.3%,3.4%,3.5%,3.6%,3.7%,3.8%,3.9%,4.0%,4.1%,4.2% , 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, or 7.0% Mg. All percentages are by weight.

[0037] In some examples, the alloys described herein include manganese (Mn) in an amount of about 0.01% to about 1.2% (e.g., about 0.1% to about 0.9%, or about 0.2% to about 0.7%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0. 30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.9 ... 1%,0.62%,0.63%,0.64%,0.65%,0.66%,0.67%,0.68%,0.69%,0.70%,0.71%,0.72%,0.73%,0.74%,0.75%,0.76%,0.77%,0.78%,0.79%,0.80%,0.81%,0.82%,0.83%,0,0.84%,0.85%,0.86%,0.87%,0.88%,0.89%,0.90%,0.91%,0 The composition may contain 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.0%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, or 1.20% Mn. All percentages are by weight.

[0038] In some examples, the alloys described herein include Si in an amount up to about 1.5 wt.% (e.g., about 0.01% to about 1.50%, about 0.20% to about 1.0%, or about 0.3% to about 0.9%) based on the total weight of the alloy.For example, alloys are 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, .38%,0.39%,0.40%,0.41%,0.42%,0.43%,0.44%,0.45%,0.46%,0.47%,0.48%,0.49%,0.50%,0.51%,0.52%,0.53%,0.54%,0.55%,0.56%,0.57%,0.58%,0.59%,0.60%,0.61%,0.62%,0.63%,0.64%,0.65%,0.66%,0.67%,0.68%,0.69%,0.70%,0.71%,0.72%,0.73%,0.74%,0.75%,0.7 6%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.0%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, The alloy may contain 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27%, 1.28%, 1.29%, 1.30%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.39%, 1.40%, 1.41%, 1.42%, 1.43%, 1.44%, 1.45%, 1.46%, 1.47%, 1.48%, 1.49%, or 1.50% Si. In some cases, Si is absent (i.e., 0%) in the alloy. All percentages are by weight.

[0039] In some examples, the alloys described herein include titanium (Ti) in an amount up to about 0.2% (e.g., about 0.01% to about 0.15%, or about 0.02% to about 0.1%) based on the total weight of the alloy. For example, the alloys may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.20% Ti. In some cases, Ti is absent (i.e., 0%) in the alloy. All percentages are expressed by weight.

[0040] In some examples, the alloys described herein include zinc (Zn) in an amount between about 0% and about 6.0% (e.g., between about 0.01% and about 5.0%, or between about 0.02% and about 3.0%) based on the total weight of the alloy. For example, alloys may be used at 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0. 72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2. It may contain 0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, or 6.0% Zn. In some cases, Zn is absent (i.e., 0%) in the alloy.All percentages are expressed as weight percent.

[0041] In some examples, the alloys described herein include chromium (Cr) in an amount up to about 0.30% (e.g., from about 0.01% to about 0.25%, or from about 0.02% to about 0.1%) based on the total weight of the alloy. For example, the alloy may contain 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.30% Cr. In some cases, Cr is absent (i.e., 0%) in the alloy. All percentages are expressed by weight.

[0042] In some examples, the alloys described herein include zirconium (Zr) in an amount of about 0% to about 0.15% (e.g., about 0.01% to about 0.1%, or about 0.02% to about 0.05%) based on the total weight of the alloy. For example, the alloys may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, or 0.15% Zr. In some cases, Zr is absent (i.e., 0%) in the alloy. All percentages are expressed by weight.

[0043] Optionally, the alloy compositions described herein may also contain other trace elements, sometimes referred to as impurities, in amounts of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less for each impurity. These impurities include, but are not limited to, Sn, Ga, Ca, Bi, Na, Pb, Li, W, Mo, Ni, V, or combinations thereof. Thus, Sn, Ga, Ca, Bi, Na, Pb, Li, W, Mo, Ni, or V may be present in the alloy in amounts of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. In some cases, the sum of all impurities does not exceed 0.15% (e.g., 0.10%). All are expressed in weight percent. The remaining percentage of the alloy is aluminum.

[0044] In some examples, alloys suitable for use in the recycled inclusion alloys described herein may be 1xxx series aluminum alloys, 2xxx series aluminum alloys, 3xxx series aluminum alloys, 4xxx series aluminum alloys, 5xxx series aluminum alloys, 6xxx series aluminum alloys, 7xxx series aluminum alloys, 8xxx series aluminum alloys, or any combination thereof. The 1xxx, 2xxx, 3xxx, 4xxx, 5xxx, 6xxx, 7xxx, or 8xxx series aluminum alloys may be modified to include amounts of Mg, Cu, and / or Si as described above.

[0045] Suitable 1xxx series aluminum alloys for use in the recycled inclusion alloys described herein include, for example, AA1050, AA1060, AA1070, AA1100, AA1100A, AA1200, AA1200A, AA1300, AA1110, AA1120, AA1230, AA1230A, AA1235, AA1435, AA1145, AA1345, AA1445, AA1150, AA1350, AA1350A, AA1450, AA1370, AA1275, AA1185, AA1285, AA1385, AA1188, AA1190, AA1290, AA1193, AA1198, and AA1199.

[0046] Suitable 2xxx series aluminum alloys for use in the recycled inclusion alloys described herein include, for example, AA2001, A2002, AA2004, AA2005, AA2006, AA2007, AA2007A, AA2007B, AA2008, AA2009, AA2010, AA2011, AA2011A, AA2111, AA2111A, AA2111B, AA2012, AA2013, AA2014, AA2015, AA2016, AA2017, AA2018, AA2019, AA2020, AA2021, AA2022, AA2023, AA2024, AA2025, AA2026, AA2027, AA2028, AA2029, AA2030, AA2031, AA2032, AA2033, AA2034, AA2035, AA2036, AA2037, AA2038, AA2039, AA2040, AA2041, AA2042, AA2043, AA2044, AA2045, AA2046, AA2047, AA2048, AA2049, AA2050, AA2051, AA2052, AA2053, AA2054, AA2055, AA2056, AA2057, AA2058, AA2059, AA2060, AA2061, AA2062, AA2063, AA2064, 013, AA2014, AA2014A, AA2214, AA2015, AA2016, AA2017, AA2017A, AA2117, AA2018, AA2218, AA2618, AA2618A , AA2219, AA2319, AA2419, AA2519, AA2021, AA2022, AA2023, AA2024, AA2024A, AA2124, AA2224, AA2224A, AA2 324, AA2424, AA2524, AA2624, AA2724, AA2824, AA2025, AA2026, AA2027, AA2028, AA2028A, AA2028B, AA2028 C, AA2029, AA2030, AA2031, AA2032, AA2034, AA2036, AA2037, AA2038, AA2039, AA2139, AA2040, AA2041, AA20 AA2097, AA2197, AA2297, AA2397, AA2098, AA2198, AA2099, and AA2199.

[0047] Suitable 3xxx series aluminum alloys for use in the recycled inclusion alloys described herein include, for example, AA3002, AA3102, AA3003, AA3103, AA3103A, AA3103B, AA3203, AA3403, AA3004, AA3004A, AA3104, AA3204, AA3304, AA3005, AA3005A, AA3105, AA3105A, AA310 5B, AA3007, AA3107, AA3207, AA3207A, AA3307, AA3009, AA3010, AA3110, AA3011, AA3012, AA3012A, AA3013, AA3014, AA3015, AA3016, AA3017, AA3019, AA3020, AA3021, AA3025, AA3026, AA3030, AA3130, and AA3065.

[0048] Suitable 4xxx series aluminum alloys for use in the recycled inclusion alloys described herein include, for example, AA4004, AA4104, AA4006, AA4007, AA4008, AA4009, AA4010, AA4013, AA4014, AA4015, AA4015A, AA4115, AA4016, AA4017, AA4018, AA4019, AA4020, AA4021, AA4026, AA4032, AA4043, AA4043A, AA4143, AA4343, AA4643, AA4943, AA4044, AA4045, AA4145, AA4145A, AA4046, AA4047, AA4047A, and AA4147.

[0049] Suitable 5xxx series aluminum alloys for use in the recycled inclusion alloys described herein include, for example, AA5005, AA5005A, AA5205, AA5305, AA5505, AA5605, AA5006, AA5106, AA5010, AA5110, AA5110A, AA5210, AA5310, AA5016, AA5017, AA5018, AA5018A, AA5019, AA5019A, AA5119 , AA5119A, AA5021, AA5022, AA5023, AA5024, AA5026, AA5027, AA5028, AA5040, AA5140, AA5041, AA5042, AA5043, AA504 9, AA5149, AA5249, AA5349, AA5449, AA5449A, AA5050, AA5050A, AA5050C, AA5150, AA5051, AA5051A, AA5151, AA5251, AA 5251A, AA5351, AA5451, AA5052, AA5252, AA5352, AA5154, AA5154A, AA5154B, AA5154C, AA5254, AA5354, AA5454, AA555 4, AA5654, AA5654A, AA5754, AA5854, AA5954, AA5056, AA5356, AA5356A, AA5456, AA5456A, AA5456B, AA5556, AA5556A, Examples include AA5556B, AA5556C, AA5257, AA5457, AA5557, AA5657, AA5058, AA5059, AA5070, AA5180, AA5180A, AA5082, AA5182, AA5083, AA5183, AA5183A, AA5283, AA5283A, AA5283B, AA5383, AA5483, AA5086, AA5186, AA5087, AA5187, and AA5088.

[0050] Suitable 6xxx series aluminum alloys for use in the recycled inclusion alloys described herein include, for example, AA6101, AA6101A, AA6101B, AA6201, AA6201A, AA6401, AA6501, AA6002, AA6003, AA6103, AA6005, AA6005A, AA6005B, AA6005C, AA6105, AA6205, AA6305, AA6006, AA6106, AA 6206, AA6306, AA6008, AA6009, AA6010, AA6110, AA6110A, AA6011, AA6111, AA6012, AA6012A, AA6013, AA6113, AA6014 , AA6015, AA6016, AA6016A, AA6116, AA6018, AA6019, AA6020, AA6021, AA6022, AA6023, AA6024, AA6025, AA6026, AA602 7, AA6028, AA6031, AA6032, AA6033, AA6040, AA6041, AA6042, AA6043, AA6151, AA6351, AA6351A, AA6451, AA6951, AA6 053, AA6055, AA6056, AA6156, AA6060, AA6160, AA6260, AA6360, AA6460, AA6460B, AA6560, AA6660, AA6061, AA6061A, A Examples include A6261, AA6361, AA6162, AA6262, AA6262A, AA6063, AA6063A, AA6463, AA6463A, AA6763, A6963, AA6064, AA6064A, AA6065, AA6066, AA6068, AA6069, AA6070, AA6081, AA6181, AA6181A, AA6082, AA6082A, AA6182, AA6091, and AA6092.

[0051]

[0033] 7xxx series aluminum alloys suitable for use in the recycled inclusion alloys described herein include, for example, AA7019, AA7020, AA7021, AA7039, AA7072, AA7075, AA7085, AA7108, AA7108A, AA7015, AA7017, AA7018, AA7019A, AA7024, AA7025, AA7028, AA7030, AA7031, AA7035, AA7035A, AA7046, AA7046A, AA7003, AA7004, AA7005, AA7009, AA7010, AA7011, AA7012, AA7014, AA7016, AA7116, AA7122, AA7023, AA7026, AA7029, AA 7129, AA7229, AA7032, AA7033, AA7034, AA7036, AA7136, AA7037, AA7040, AA7140, AA7041, AA 7049, AA7049A, AA7149, AA7249, AA7349, AA7449, AA7050, AA7050A, AA7150, AA7250, AA7055, A These include A7155, AA7255, AA7056, AA7060, AA7064, AA7065, AA7068, AA7168, AA7175, AA7475, AA7076, AA7178, AA7278, AA7278A, AA7081, AA7181, AA7185, AA7090, AA7093, AA7095, and AA7099.

[0052] Suitable 8xxx series aluminum alloys for use in the recycled inclusion alloys described herein include, for example, AA8005, AA8006, AA8007, AA8008, AA8010, AA8011, AA8011A, AA8111, AA8211, AA8112, AA8014, AA8015, AA8016, AA8017, AA8018, AA8019, Examples include AA8021, AA8021A, AA8021B, AA8022, AA8023, AA8024, AA8025, AA8026, AA8030, AA8130, AA8040, AA8050, AA8150, AA8076, AA8076A, AA8176, AA8077, AA8177, AA8079, AA8090, AA8091, and AA8093.

[0053] A variety of products can be produced that include the recycled inclusion alloys described herein. In some examples, the prepared products that include the recycled inclusion alloys described herein can be clad products that include a core layer and one or more clad layers. The core layer has a first side and a second side, and one or more clad layers can be bonded to the first side or the second side of the core layer. In some examples, the core layer is covered on only one side (i.e., one clad layer is present in the clad aluminum alloy product). In other examples, the core layer is covered on both sides (i.e., two clad layers are present in the clad aluminum alloy product).

[0054] The cladding layer(s) may be attached to the core layer by, for example, direct chill cocasting (i.e., fusion casting) as described in U.S. Pat. Nos. 7,748,434 and 8,927,113, which are incorporated by reference in their entireties, by hot and cold rolling a composite ingot as described in U.S. Pat. No. 7,472,740, which is incorporated by reference in its entirety, or by roll bonding to achieve the requisite metallurgical bond between the core and the cladding.

[0055] The recycled inclusion alloys described herein may be used as a core layer or as one or more clad layers. Optionally, the one or more clad layers may include a 1xxx series aluminum alloy, a 2xxx series aluminum alloy, a 3xxx series aluminum alloy, a 4xxx series aluminum alloy, a 5xxx series aluminum alloy, a 6xxx series aluminum alloy, a 7xxx series aluminum alloy, or an 8xxx series aluminum alloy. In some examples, clad products are prepared from recycled inclusion alloys described herein as the core and a 5xxx or 6xxx series aluminum alloy as one or both of the clad layers.

[0056] The aluminum alloy products described herein may have any suitable gauge. The recycled inclusion alloy may be cast and processed into various sizes and thicknesses, such as foils (e.g., less than about 0.20 mm), sheets (e.g., about 0.20 mm to 4.0 mm), shades (e.g., about 4.0 mm to 15.0 mm), or plates (e.g., greater than about 15.0 mm), although other thicknesses and ranges may be used as well. In some examples, the aluminum alloy products described herein may be provided and delivered to a customer or end user at an intermediate gauge (e.g., a gauge that is further reduced by the customer or end user as needed). In some examples, the aluminum alloy products described herein may be provided and delivered to a customer or end user at a final gauge (e.g., a gauge that is not further reduced by the customer or end user).

[0057] Products including the recycled inclusion alloys described herein can include a hydrogen content of 0.15 mL / 100 grams or less (e.g., 0.10 mL / 100 grams or less, 0.08 mL / 100 grams or less, or 0.06 mL / 100 grams or less). For example, the amount of hydrogen contained in the aluminum alloy product may be about 0.15 mL / 100 grams, 0.14 mL / 100 grams, 0.13 mL / 100 grams, 0.12 mL / 100 grams, 0.11 mL / 100 grams, 0.1 mL / 100 grams, 0.09 mL / 100 grams, 0.08 mL / 100 grams, 0.07 mL / 100 grams, 0.06 mL / 100 grams, 0.05 mL / 100 grams, 0.04 mL / 100 grams, 0.03 mL / 100 grams, 0.02 mL / 100 grams, or 0.01 mL / 100 grams, or less. Optionally, the hydrogen content of the product is at least 0.08 mL / 100 grams. For example, the hydrogen content can be 0.08 mL / 100 grams to 0.25 mL / 100 grams, 0.1 mL / 100 grams to 0.20 mL / 100 grams, or 0.12 mL / 100 grams to 0.18 mL / 100 grams. The amount of dissolved hydrogen present affects the properties of the resulting metal product. During casting, dissolved hydrogen can affect the castability of the metal product (e.g., resistance to hot cracking), as well as the mechanical properties of the resulting metal product (e.g., bending strength, toughness, fatigue strength, maximum elongation, crash resistance, surface quality, corrosion resistance, and other properties). Dissolved hydrogen can affect solidification and introduce porosity into the cast metal product. Products prepared from recycled inclusion alloys described herein having the above hydrogen contents are not subject to these deleterious effects.

[0058] The recycled aluminum alloy products described herein include iron-containing intermetallic particles, also referred to herein as Fe-containing components. In some cases, the iron-containing intermetallic particles are spherical. The Fe-containing components can have a length in the range of about 0.6 μm to about 1.8 μm (e.g., about 0.7 μm to about 1.7 μm or about 0.8 μm to about 1.6 μm).

[0059] The aluminum alloy products described herein contain intermetallic particles having a low aspect ratio (e.g., ratio of width to height). In some cases, a low aspect ratio is a ratio of about 3 or less (e.g., about 2.5 or less, about 2 or less, or about 1.5 or less). In particular, the intermetallic particles are round or spherical in shape. An aspect ratio of 1 (e.g., near circular cross section, i.e., spherical particles) is a preferred Fe-containing intermetallic particle shape for mechanical properties, e.g., bending, forming, crushing, and / or crash testing. These intermetallic particles enhance the desired mechanical properties of the product.

[0060] In some cases, the metal products described herein may have a yield strength of at least about 100 MPa. For example, the metal products described herein may have a yield strength of about 100 MPa to about 300 MPa (e.g., about 150 MPa to about 250 MPa). In some cases, the yield strength may be about 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa, 220 MPa, 230 MPa, 240 MPa, 250 MPa, 260 MPa, 270 MPa, 280 MPa, 290 MPa, or 300 MPa.

[0061] In some cases, the metal products described herein may have an ultimate tensile strength of at least about 210 MPa. For example, the metal products described herein may have an ultimate tensile strength of about 210 MPa to about 350 MPa (e.g., about 250 MPa to about 325 MPa). In some cases, the ultimate tensile strength may be about 210 MPa, 220 MPa, 230 MPa, 240 MPa, 250 MPa, 260 MPa, 270 MPa, 280 MPa, 290 MPa, 300 MPa, 310 MPa, 320 MPa, 330 MPa, 340 MPa, or 350 MPa.

[0062] In some cases, the metal products described herein may have a uniform elongation of at least about 18%. For example, the metal products described herein may have a uniform elongation of about 18% to about 25% (e.g., about 19% to about 23%). In some cases, the uniform elongation may be about 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, or 25%.

[0063] In some cases, the metal products described herein may have a total elongation of at least about 20.5%. For example, the metal products described herein may have a total elongation of about 20.5% to about 27.5% (e.g., about 22% to about 26%). In some cases, the total elongation may be about 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, or 27.5%.

[0064] Method of preparation The recycled inclusion alloy can be used to cast various metal casting products, such as billets, ingots, or strips. Prior to casting, the liquid metal from the recycled scrap can be optionally degassed to reduce the amount of hydrogen dissolved in the liquid metal. In some cases, degassing can include bubbling a gas, for example an inert gas (e.g., argon or nitrogen), into the liquid metal to induce dissolution of hydrogen bubbles into the gas and thus out of the liquid metal. Any suitable degassing technique can be used.

[0065] After the optional degassing step, the recycled inclusion alloy described herein may be cast using any suitable casting method known to those skilled in the art. As some non-limiting examples, the casting process may include a direct chill (DC) casting process or a continuous casting (CC) process. A direct chill casting system may include a mold cavity and a retractable bottom block. Once the liquid metal has solidified in the mold cavity, the bottom block may be pulled away from the mold cavity to support the solidified ingot (e.g., the initial ingot), which continues to grow in length continuously by solidifying metal at the surface of the ingot, and the ingot continues to solidify throughout. A continuous casting system may include a pair of moving opposing casting surfaces (e.g., moving opposing belts, rolls, or blocks), a casting cavity between the pair of moving opposing casting surfaces, and a molten metal injector. The molten metal injector may have an end opening from which molten metal may exit the molten metal injector and be injected into the casting cavity. Certain aspects of the present disclosure may include continuous casting using a twin belt continuous caster or a twin roll continuous caster.

[0066] After casting, the metal product (e.g., metal sheet, plate, or other cast product) can be rolled to a desired gauge. Metal products cast from the recycled inclusion alloys disclosed herein may have higher than normal concentrations of alloying elements. In conventional rolling techniques, the metal product is passed through a hot rolling process followed by a cold rolling process. Hot rolling is performed at a temperature above the recrystallization temperature of the metal, and cold rolling is performed at a temperature below the recrystallization temperature. Cold rolling requires the metal to be deformed below the recrystallization temperature, so that the metal is strain hardened by the formation of dislocations within the matrix of the metal.

[0067] Through unobvious testing and experimentation, it has been found that metal products cast using recycled inclusion alloys disclosed herein having higher than normal concentrations of alloying elements can be conveniently hot rolled to a gauge (e.g., intermediate or final gauge, as further described above), thus eliminating the need for one or more cold rolling steps to transform the metal product to a desired gauge. Optionally, the metal products described herein can be delivered in any suitable gauge as described herein. For example, the metal products can be delivered to a customer (e.g., an original equipment manufacturer) or other suitable end user in intermediate or final gauge. In some cases, hot rolling to gauge can include receiving the metal product from a continuous casting apparatus, but this is not necessarily the case. In some cases, it has been found that hot rolling to gauge can result in improved metallurgical properties over techniques including cold rolling to gauge without hot rolling, and hot rolling to intermediate gauge followed by cold rolling to final gauge. Furthermore, casting metal products using a continuous casting apparatus such as the casting apparatus disclosed herein can facilitate hot rolling to gauge without having to resort to subsequent cold rolling. In some cases, cast metal products are cold rolled during processing.

[0068] These illustrative examples are provided to introduce the reader to the general subject matter described herein and are not intended to limit the scope of the disclosed concepts. The following section describes various additional features and examples with reference to the drawings, which should not be used to limit the disclosure as exemplary embodiments, in which like numbers refer to like elements and directional descriptions are used to describe exemplary embodiments. Elements included in the examples herein may not be drawn to scale.

[0069] 1 is a flow chart illustrating a process 100 for casting and hot rolling metal products from recycled scrap, according to certain embodiments of the present disclosure. In block 102, recycled scrap, such as UBC scrap, is melted. The scrap can be melted in any suitable vessel, such as a rotary furnace, a crucible furnace, or any other suitable heating device. The liquid metal obtained from the recycled scrap may contain alloying elements that make the liquid metal a non-standard alloy, for example, an alloy not typically used for beverage parts (e.g., can ends and bodies) or automotive parts (e.g., automotive hood liners).

[0070] At block 104, additional alloying elements can be added to the liquid metal to obtain a modified liquid metal having a desired concentration of the alloying elements. The addition of the alloying elements can include melting the raw elements or a mixture of aluminum and the alloying elements into the liquid metal from block 102. After the addition of the alloying elements, the modified liquid metal can have a desired composition of alloying elements and aluminum.

[0071] In block 105, the reformed liquid metal from block 104 may be degassed to reduce the amount of dissolved gas in the reformed liquid metal. Degassing the reformed liquid metal may include reducing the concentration of hydrogen in the reformed liquid metal to a desired concentration, such as the concentrations identified above (e.g., 0.25 mL / 100 g or less). For example, the amount of hydrogen contained in the reformed liquid metal after degassing may be about 0.25 mL / 100 grams, 0.24 mL / 100 grams, 0.23 mL / 100 grams, 0.22 mL / 100 grams, 0.21 mL / 100 grams, 0.2 mL / 100 grams, 0.19 mL / 100 grams, 0.18 mL / 100 grams, 0.17 mL / 100 grams, 0.16 mL / 100 grams, 0. The degassing volume may be 15 mL / 100 grams, 0.14 mL / 100 grams, 0.13 mL / 100 grams, 0.12 mL / 100 grams, 0.11 mL / 100 grams, 0.1 mL / 100 grams, 0.09 mL / 100 grams, 0.08 mL / 100 grams, 0.07 mL / 100 grams, 0.06 mL / 100 grams, or 0.05 mL / 100 grams, or less. Any suitable technique may be used to degas the modified liquid metal.

[0072] In block 106, the modified liquid metal from block 105 can be cast using a continuous casting apparatus to obtain an intermediate metal product 116. The modified liquid metal cast in block 106 can contain little or no primary aluminum. In some cases, the modified liquid metal can contain about 50%, 40%, 30%, 20%, 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, or 1% or less of primary aluminum.

[0073] In some cases, instead of casting using a continuous casting apparatus as described with reference to block 106, the modified liquid metal from block 105 can be cast using a direct chill casting apparatus at block 107 and, optionally, rolled to an intermediate gauge. The resulting metal product of intermediate gauge can be intermediate metal product 116. Rolling to intermediate gauge can include reducing the thickness of the direct chill cast ingot using any suitable equipment, such as using a reversing mill. In some cases, the modified liquid metal can include about 50%, 40%, 30%, 20%, 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, or 1% or less of primary aluminum.

[0074] At block 108, the intermediate metal product 116 may be hot rolled to a gauge. Hot rolling to a gauge may include applying pressure to the intermediate metal product 116 by one or more work rolls at an elevated temperature, e.g., at or above the recrystallization temperature of the intermediate metal product 116, although lower temperatures may also be used. For example, in some cases, hot rolling is performed at a temperature of about 400° C. or above, although other temperatures may be used. As a result of the hot rolling at block 108, the intermediate metal product 116 is reduced in thickness from an as-cast gauge to a desired gauge for delivery to an original equipment manufacturer (OEM) or other user. In one example, the as-cast gauge of the intermediate metal product 116 is about 10 mm, while the final gauge (e.g., the desired gauge for delivery to an OEM) is about 1.5 mm, although other gauges may be used. During hot rolling, the metal product may pass through any number of rollers implemented in any number of roll stands. After hot rolling, the metal product may be considered a hot rolled metal product 118. The hot rolled metal product 118 may have a T4 or O temper.

[0075] In some cases, the metal product may be preheated prior to hot rolling. For example, the metal product may be preheated to a temperature equal to or greater than the recrystallization temperature. In one example, the metal product may be preheated to a temperature of about 400°C or greater, 450°C, 500°C, 550°C, 560°C, 570°C, or 580°C. In some cases, the metal product may be preheated in an oven at 400°C to 580°C for 5 minutes to 15 hours. In some cases, the oven temperature may be about 550°C to 570°C and the time may be 30 minutes to 6 hours. In some cases, the oven temperature may be about 560°C and the time may be 30 minutes to 6 hours. In some cases, the preheating may be at other temperatures and other times.

[0076] In optional block 112, the hot rolled metal product 118 may be heat treated. In some cases, the heat treatment may include annealing. In block 112, the hot rolled metal product 118 may be reheated to or above the annealing temperature for a suitable period of time. For example, heating the hot rolled metal product 118 to a temperature of 350° C. or above for about an hour may result in the metal product being in the O temper.

[0077] In some cases, the heat treatment may include solutionizing the hot rolled metal product 118 to bring certain alloying elements, such as silicon and copper, back into solution. As part of the solutionizing, the reheated metal product may be quenched to help keep the alloying elements in solution.

[0078] Heat treatment can improve the metallurgical and / or mechanical properties of a metal product. For example, annealing can improve the formability of a metal product.

[0079] At block 114, the metal product may be rolled for delivery to the OEM. In some cases, the metal product may be further processed before delivery or may proceed directly to part manufacturing without being rolled.

[0080] 2 is a flow chart illustrating a process 200 for casting and cold rolling metal products from recycled scrap, such as UBC scrap, according to certain embodiments of the present disclosure. In block 202, recycled scrap, such as UBC scrap, is melted 202. The scrap can be melted in any suitable vessel, such as a rotary furnace, a crucible furnace, or any other suitable heating device. The liquid metal obtained from the recycled scrap may contain alloying elements that make the liquid metal a non-standard alloy, for example, an alloy not typically used for beverage parts (e.g., can ends and bodies) or automotive parts (e.g., automotive hood or deck lid inners).

[0081] At block 204, additional alloying elements may be added to the liquid metal to achieve a modified liquid metal having a desired concentration of alloying elements. The addition of the alloying elements may include melting raw elements or a mixture of aluminum and alloying elements into the liquid metal from block 202. After the addition of the alloying elements, the modified liquid metal may have a desired composition of alloying elements and aluminum.

[0082] In block 205, the reformed liquid metal from block 204 may be degassed to reduce the amount of dissolved gas in the reformed liquid metal. Degassing the reformed liquid metal may include reducing the concentration of hydrogen in the reformed liquid metal to a desired concentration, such as the concentrations identified above (e.g., 0.25 mL / 100 g or less). For example, the amount of hydrogen contained in the reformed liquid metal after degassing may be about 0.25 mL / 100 grams, 0.24 mL / 100 grams, 0.23 mL / 100 grams, 0.22 mL / 100 grams, 0.21 mL / 100 grams, 0.2 mL / 100 grams, 0.19 mL / 100 grams, 0.18 mL / 100 grams, 0.17 mL / 100 grams, 0.16 mL / 100 grams, 0. The degassing volume may be 15 mL / 100 grams, 0.14 mL / 100 grams, 0.13 mL / 100 grams, 0.12 mL / 100 grams, 0.11 mL / 100 grams, 0.1 mL / 100 grams, 0.09 mL / 100 grams, 0.08 mL / 100 grams, 0.07 mL / 100 grams, 0.06 mL / 100 grams, or 0.05 mL / 100 grams, or less. Any suitable technique may be used to degas the modified liquid metal.

[0083] In block 206, the modified liquid metal from block 205 can be cast using a continuous casting apparatus to obtain an intermediate metal product 216. The modified liquid metal cast in block 206 can contain little or no primary aluminum. In some cases, the modified liquid metal can contain about 50%, 40%, 30%, 20%, 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, or 1% or less of primary aluminum.

[0084] At block 208, the intermediate metal product 216 may be cold rolled to a gauge. Cold rolling to a gauge may include applying pressure to the intermediate metal product 216 by one or more work rolls at a temperature below the recrystallization temperature of the intermediate metal product 216. For example, in some cases, cold rolling is performed at a temperature below about 400° C., although other temperatures may be used. As a result of the cold rolling at block 208, the intermediate metal product 216 is reduced in thickness from an as-cast gauge to a desired gauge for delivery to an OEM or other user. In one example, the as-cast gauge of the intermediate metal product 216 may be about 10 mm, while the final gauge (e.g., the desired gauge for delivery to an OEM) may be about 1.5 mm, although other gauges may be used. During cold rolling, the metal product may pass through any number of rollers implemented in any number of roll stands. After cold rolling, the metal product may be considered a cold rolled metal product 218. The cold rolled metal product 218 may have an H temper.

[0085] In optional block 212, the cold rolled metal product 218 may be heat treated. In some cases, the heat treatment may include annealing. In block 212, the cold rolled metal product 218 may be reheated to or above the annealing temperature for a suitable period of time. For example, heating the cold rolled metal product 218 to a temperature of 350° C. or above for about an hour may result in the metal product being in the O temper.

[0086] In some cases, the heat treatment may include solutionizing the cold rolled metal product 218 to bring certain alloying elements, such as silicon and copper, back into solution. As part of the solutionizing, the reheated metal product may be quenched to help keep the alloying elements in solution.

[0087] Heat treatment can improve the metallurgical and / or mechanical properties of a metal product. For example, annealing can improve the formability of a metal product.

[0088] At block 214, the metal product may be rolled for delivery to the OEM. In some cases, the metal product may be further processed prior to delivery or may proceed directly to part manufacturing without being rolled.

[0089] 3 is a flow chart illustrating a process 300 for casting and rolling metal products from recycled scrap, such as UBC scrap, using cold and hot rolling, according to certain embodiments of the present disclosure. In block 302, recycled scrap, such as UBC scrap, is melted 302. The scrap can be melted in any suitable vessel, such as a rotary furnace, a crucible furnace, or any other suitable heating device. The liquid metal obtained from the recycled scrap may contain alloying elements that make the liquid metal a non-standard alloy, for example, an alloy not typically used for beverage parts (e.g., can ends and bodies) or automotive parts (e.g., automotive hood liners).

[0090] At block 304, additional alloying elements may be added to the liquid metal to achieve a modified liquid metal having a desired concentration of the alloying elements. The addition of the alloying elements may include melting the raw elements or a mixture of aluminum and the alloying elements into the modified liquid metal from block 302. After the addition of the alloying elements, the modified liquid metal may have a desired composition of alloying elements and aluminum.

[0091] In block 305, the reformed liquid metal from block 304 may be degassed to reduce the amount of dissolved gas in the reformed liquid metal. Degassing the reformed liquid metal may include reducing the concentration of hydrogen in the reformed liquid metal to a desired concentration, such as the concentrations identified above (e.g., 0.25 mL / 100 g or less). For example, the amount of hydrogen contained in the reformed liquid metal after degassing may be about 0.25 mL / 100 grams, 0.24 mL / 100 grams, 0.23 mL / 100 grams, 0.22 mL / 100 grams, 0.21 mL / 100 grams, 0.2 mL / 100 grams, 0.19 mL / 100 grams, 0.18 mL / 100 grams, 0.17 mL / 100 grams, 0.16 mL / 100 grams, 0. The degassing volume may be 15 mL / 100 grams, 0.14 mL / 100 grams, 0.13 mL / 100 grams, 0.12 mL / 100 grams, 0.11 mL / 100 grams, 0.1 mL / 100 grams, 0.09 mL / 100 grams, 0.08 mL / 100 grams, 0.07 mL / 100 grams, 0.06 mL / 100 grams, or 0.05 mL / 100 grams, or less. Any suitable technique may be used to degas the modified liquid metal.

[0092] In block 306, the modified liquid metal from block 305 can be cast using a continuous casting apparatus to obtain an intermediate metal product 316. The modified liquid metal cast in block 306 can contain little or no primary aluminum. In some cases, the modified liquid metal can contain about 50%, 40%, 30%, 20%, 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, or 1% or less of primary aluminum.

[0093] In some cases, instead of casting using a continuous casting apparatus as described with reference to block 306, the modified liquid metal from block 305 can be cast using a direct chill casting apparatus in block 307 and, optionally, rolled to an initial intermediate gauge. The resulting metal product of intermediate gauge can be intermediate metal product 316. Rolling to intermediate gauge can include reducing the thickness of the direct chill cast ingot using any suitable equipment, such as using a reversing mill. In some cases, the modified liquid metal can include about 50%, 40%, 30%, 20%, 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, or 1% or less of primary aluminum.

[0094] At block 308, the intermediate metal product 316 may be hot rolled to reduce thickness to an intermediate gauge. Hot rolling to an intermediate gauge may include applying pressure to the intermediate metal product 316 by one or more work rolls at an elevated temperature, for example, at a temperature equal to or greater than the recrystallization temperature of the intermediate metal product 316, although lower temperatures may also be used. For example, in some cases, hot rolling is performed at a temperature of about 400° C. or greater, although other temperatures may be used. As a result of the hot rolling at block 308, the intermediate metal product 316 is reduced in thickness from an as-cast gauge to an intermediate gauge. In one example, the as-cast gauge of the intermediate metal product 316 may be about 10 mm, while the intermediate gauge may be about 4 mm, although other gauges may be used. During hot rolling, the metal product may pass through any number of rollers implemented in any number of roll stands. After hot rolling, the metal product may be considered a hot rolled metal product 318. The hot rolled metal product 318 may have a T4 or O temper.

[0095] In some cases, the metal product may be preheated prior to hot rolling. For example, the metal product may be preheated to a temperature equal to or greater than the recrystallization temperature. In one example, the metal product may be preheated to a temperature equal to or greater than about 400°C, 450°C, 500°C, 550°C, 560°C, 570°C, or 580°C. In some cases, the metal product may be preheated in an oven at 400°C to 580°C for 5 minutes to 15 hours. In some cases, the oven temperature may be about 550°C to 570°C and the time may be 30 minutes to 6 hours. In some cases, the oven temperature may be about 560°C and the time may be 30 minutes to 6 hours. In some cases, the preheating may be at other temperatures and other times.

[0096] At block 310, the hot rolled metal product 318 may be cold rolled from an intermediate gauge to a final gauge. Cold rolling to gauge may include applying pressure to the hot rolled intermediate metal product 318 by one or more work rolls at a temperature below the recrystallization temperature of the hot rolled intermediate metal product 318. For example, in some cases, cold rolling is performed at a temperature below about 400° C., although other temperatures may be used. As a result of the cold rolling at block 310, the hot rolled metal product 318 is reduced in thickness from the intermediate gauge to a desired gauge for delivery to an OEM or other user. In one example, the intermediate gauge of the hot rolled metal product 318 may be about 4 mm, while the final gauge (e.g., the desired gauge for delivery to an OEM) is about 1.5 mm, although other gauges may be used. During cold rolling, the metal product may pass through any number of rollers implemented in any number of roll stands. After cold rolling, the metal product may be considered a cold rolled metal product 319. The cold rolled metal product 319 may have a T3 temper.

[0097] In optional block 312, the cold rolled metal product 318 may be heat treated. In some cases, the heat treatment may include annealing. In block 312, the cold rolled metal product 319 may be reheated to or above the annealing temperature for a suitable period of time. For example, heating the cold rolled metal product 319 to a temperature of 350° C. or above for about an hour may result in the metal product being in the O temper.

[0098] In some cases, the heat treatment may include solutionizing the cold rolled metal product 319 to bring certain alloying elements, such as silicon and copper, back into solution. As part of the solutionizing, the reheated metal product may be quenched to help keep the alloying elements in solution.

[0099] Heat treatment can improve the metallurgical and / or mechanical properties of a metal product. For example, annealing can improve the formability of a metal product.

[0100] At block 314, the metal product may be rolled for delivery to the OEM. In some cases, the metal product may be further processed prior to delivery or may proceed directly to part manufacturing without being rolled.

[0101] 4 is a schematic diagram illustrating a separate metal casting and rolling system 400 according to certain embodiments of the present disclosure. The separate metal casting and rolling system 400 may be particularly suitable for casting and rolling metal from recycled scrap, such as UBC scrap. For example, the separate metal casting and rolling system 400 may be used to perform the process 100 of FIG. 1.

[0102] The separated metal casting and rolling system 400 may include a casting system 402, a storage system 404, and a hot rolling system 406. The separated metal casting and rolling system 400 may be considered a single continuous processing line with separate subsystems. Metal products 410 cast by the casting system 402 may continue downstream through the storage system 404, and the hot rolling system 406. The separated metal casting and rolling system 400 may be considered continuous because the metal products 410 may be continuously produced by the casting system 402, stored by the storage system 404, and hot rolled by the hot rolling system 406. In some cases, the separated metal casting and rolling system 400 may be located within a single building or facility, while in some cases, the subsystems of the separated metal casting and rolling system 400 may be located remotely from one another. In some cases, a single casting system 402 may be associated with one or more storage systems 404 and one or more hot rolling systems 406, thereby allowing the casting system 402 to operate continuously at much higher speed rates than a single storage system 404 or hot rolling system 406.

[0103] The casting system 402 includes a continuous casting apparatus, such as a belt continuous caster 408 (e.g., a twin-belt caster), that continuously casts a metal product 410. The casting system 402 can optionally include a rapid quench system 414 located immediately downstream or immediately after the belt continuous caster 408. The casting system 402 can include a winding apparatus that can wind the metal product 410 into an intermediate coil 412. Although the continuous casting system 402 shown in FIG. 4 is a belt continuous caster, other continuous casting systems, such as a twin roll continuous casting system, can be used.

[0104] The intermediate coil 412 can accumulate and transport to another location a portion of the metal product 410 exiting the belt continuous caster 408, and then a new intermediate coil 412 can be formed from additional metal product 410 exiting the belt continuous caster 408, thus allowing the belt continuous caster 408 to operate continuously or semi-continuously.

[0105] The intermediate coil 412 may be provided directly to the hot rolling system 406 or may be stored and / or processed in the storage system 404. The storage system 404 may include a variety of storage mechanisms, e.g., vertical or horizontal storage mechanisms, and cyclic or continuously rotating storage mechanisms. In some cases, the intermediate coil 412 may be preheated in a preheater 416 (e.g., a furnace) when stored in the storage system 404. Preheating may be performed during some or all of the time the intermediate coil 412 is in the storage system 404. After storage in the storage system 404, the metal product 410 may be provided to the hot rolling system 406.

[0106] The hot rolling system 406 can reduce the thickness of the metal product 410 from an as-cast gauge to a desired gauge for delivery. In some cases, the desired gauge for delivery can be between 0.7 mm and 4.5 mm or so, or between about 1.5 mm and 3.5 mm or so. The hot rolling system 406 can include a series of hot rolling stands 418 to reduce the thickness of the metal product 410. In some cases, the series of hot rolling stands 418 can include a single hot rolling stand, although any number of hot rolling stands can be used, e.g., two, three, or more. In some cases, using more (e.g., three, four, or more) hot rolling stands can result in a better surface quality for a given overall reduction in thickness (e.g., reduction in thickness from before the first hot rolling stand to after the last hot rolling stand) because each roll stand therefore needs to reduce the thickness of the metal by a smaller amount, and thus generally results in fewer surface defects being introduced into the metal product. However, one or two hot rolling stands may be used to achieve suitable surface quality. The hot rolling system 406 may further perform other processing of the metal product, such as surface finishing (e.g., texturing), preheating, and heat treatment. The metal product 410 exiting the hot rolling system 406 may be provided directly to further processing equipment (e.g., a die cutter or bending machine) or may be wound into a distributable coil 420 (e.g., a finished coil). As used herein, the term distributable may describe a metal product, such as a coiled metal product, that has properties desired by a consumer of the metal product. For example, the distributable coil 420 may include a coiled metal product that has physical and / or chemical properties that meet the specifications of an original equipment manufacturer. The distributable coil 420 may be any suitable temper, including a W temper, a T temper, or an O temper. The distributable coil 420 may be stored, sold, or shipped as needed.

[0107] The separated metal casting and rolling system 400 shown in FIG. 4 allows for the speed of the casting system 402 to be decoupled from the speed of the hot rolling system 406. As shown, the separated metal casting and rolling system 400 uses a storage system 404 for storing intermediate coils 412, where metal products 410 exiting a belt continuous caster 408 are wound into separate units and stored until the hot rolling system 406 is available to process them. Instead of storing intermediate coils 412, in some cases, the storage system 404 uses an in-line accumulator that receives the metal products 410 from the casting system 402 at a first speed and accumulates the metal products 410 between a series of moving rollers to allow the continuous metal products 410 to be fed to the hot rolling system 406 at a second speed, different from the first speed. The in-line accumulator can be sized to accommodate the difference between the first and second speeds for a predetermined time based on the desired casting duration of the casting system 402. In systems where it is desired that the casting system 402 operate continuously, a coil-based storage system 404 may be desirable.

[0108] 5 is a schematic diagram illustrating a continuous casting system 500 according to certain embodiments of the present disclosure. The continuous casting system 500 includes a continuous casting apparatus, such as a belt continuous caster 508. The continuous casting system 500 may be particularly suitable for casting and rolling metal from UBC scrap. For example, the continuous casting system 400 may be used to perform casting at blocks 106, 206, or 306 of FIGS. 1, 2, or 3, respectively.

[0109] The belt caster 508 includes an opposing belt 534 capable of extracting heat from the liquid metal 536 (e.g., modified liquid metal) at a cooling rate sufficient to solidify the liquid metal 536, which exits the belt caster 508 as a metal product 510. The liquid metal 536 can be modified liquid metal derived from recycled scrap, such as UBC scrap, as described herein.

[0110] The belt caster 508 can be operated at any desired casting speed. The opposing belt 534 can be made of any suitable material, although in some cases, the belt 534 is made of copper. A cooling system within the belt caster 508 can extract sufficient heat from the liquid metal 536 so that the metal product 510 exiting the belt caster 508 has a temperature between 200-530°C, although other ranges can be used.

[0111] In some cases, rapid solidification and rapid cooling can be achieved by using a belt caster 508 configured to extract sufficient heat from the metal such that the metal product 510 exiting the belt caster 508 has a temperature below 200° C. In other cases, rapid post-cast cooling can be achieved by a quench system 514 located immediately downstream or immediately after the belt caster 508. The quench system 514 can extract sufficient heat from the metal product 510 such that the metal product exits the quench system 514 at a temperature of 100° C. or less, despite the temperature at which the metal product 510 exits the belt caster 508. As an example, the quench system 514 can be configured to reduce the temperature of the metal product 510 to 100° C. or less within about 10 seconds.

[0112] The quenching system 514 may include one or more nozzles 540 for delivering coolant 542 to the metal product 510. The coolant 542 may be supplied to the nozzles 540 from a coolant source 546 coupled to the nozzles 540 by suitable piping. The quenching system 514 may include one or more valves 544, including a valve 544 associated with the one or more nozzles 540 and / or a valve 544 associated with the coolant source 546, to regulate the amount of coolant 542 applied to the metal product 510. In some cases, the coolant source 546 may include a temperature control device for setting a desired temperature of the coolant 542. A controller 552 may be operably coupled to the valves 544, the coolant source 546, and / or the sensor 550 to control the quenching system 514. The sensor 550 may be any suitable sensor for determining a temperature of the metal product 510, such as the temperature of the metal product 510 as it exits the quenching system 514. Based on the detected temperature, the controller 552 can adjust the temperature of the coolant 542 or the flow rate of the coolant 542 to maintain the temperature of the metal product 510 as it exits the quenching system 514 within desired parameters (e.g., below 100°C).

[0113] The quench system 514 can be positioned to begin cooling the metal product 510 at a distance 548 downstream from where the metal product 510 exits the belt caster 508. The distance 548 can be as small as practicable. In some cases, the distance 548 is 5 m, 4 m, 3 m, 2 m, 1 m, 50 cm, 25 cm, 20 cm, 15 cm, 10 cm, 5 cm, 2.5 cm, or 1 cm, or less.

[0114] The metal product 510 exiting the quench system 514 may be wound into an intermediate coil by a winding device. In some cases, the metal product 510 may continue directly into hot rolling.

[0115] Examples of suitable products and methods As used hereinafter, any reference to a series of examples should be understood as a reference to each of those examples in isolation (e.g., "Examples 1-4" should be understood as "Examples 1, 2, 3, or 4").

[0116] Example 1 describes a metal casting method that includes melting recycled aluminum in a liquid metal, adding alloying elements to the liquid metal to form a modified liquid metal, the alloying elements including magnesium, silicon, or copper, casting the modified liquid metal into a metal product, the modified liquid metal including at least 50% recycled aluminum, and rolling the metal product.

[0117] Example 2 is any preceding or subsequent exemplary process, where rolling includes hot rolling the metal product to a gauge for delivery.

[0118] Example 3 is a method of the preceding or following example, where the gauge for delivery is an intermediate gauge.

[0119] Example 4 is a method of preceding or following examples, where the gauge for delivery is the final gauge.

[0120] Example 5 is any preceding or subsequent exemplary process, where rolling includes cold rolling the metal product to a gauge for delivery.

[0121] Example 6 is a method of the preceding or following example, where the gauge for delivery is the intermediate gauge.

[0122] Example 7 is a method of the preceding or following example, where the gauge for delivery is the final gauge.

[0123] Example 8 is any preceding or succeeding exemplary process in which rolling includes hot rolling and cold rolling of a metal product.

[0124] Example 9 is any preceding or subsequent exemplary process, wherein the modified liquid metal comprises magnesium in an amount up to about 7 wt. %.

[0125] Example 10 is any preceding or subsequent exemplary process, wherein the modified liquid metal comprises magnesium in an amount of at least about 1.5 wt. %.

[0126] Example 11 is any preceding or subsequent exemplary process, wherein the modified liquid metal includes magnesium in an amount between about 1.5% and about 4% by weight.

[0127] Example 12 is any preceding or subsequent exemplary process further comprising reheating the metal product after rolling to an annealing temperature, the annealing temperature being below the solidus temperature of the metal product.

[0128] Example 13 is any preceding or subsequent exemplary method, where casting includes continuously casting the modified liquid metal.

[0129] Example 14 is any of the preceding or subsequent exemplary methods, where casting includes direct chill casting of the modified liquid metal.

[0130] Example 15 is any preceding or subsequent exemplary process in which the recycled aluminum includes post-consumer beverage can scrap containing a mixture of recycled metals from can ends and can bodies.

[0131] Example 16 is any preceding or subsequent exemplary process, wherein the modified liquid metal contains at least 60% recycled aluminum.

[0132] Example 17 is any preceding or subsequent exemplary process, wherein the modified liquid metal contains at least 80% recycled aluminum.

[0133] Example 18 is any preceding or subsequent exemplary process, wherein the modified liquid metal contains a hydrogen content of 0.25 mL / 100 grams or less.

[0134] Example 19 is a metal product cast from recycled materials according to a method including any preceding or succeeding examples.

[0135] Example 20 is a metal product comprising an aluminum alloy containing approximately 0.01 wt%-1.0 wt% Cu, 0.15 wt%-0.8 wt% Fe, 0.5 wt%-7.0 wt% Mg, 0.01 wt%-1.2 wt% Mn, up to 1.5 wt% Si, up to 0.15 wt% impurities, and Al, wherein the metal product is cast from a modified liquid metal containing at least 50% recycled aluminum.

[0136] Example 21 is any of the preceding or subsequent exemplary metal products, wherein the aluminum alloy includes approximately 0.1-0.9 wt.% Cu, 0.25-0.7 wt.% Fe, 1.0-5.0 wt.% Mg, 0.1-0.9 wt.% Mn, 0.01-1.0 wt.% Si, 0.01-0.15 wt.% Ti, 0.01-5.0 wt.% Zn, 0.01-0.25 wt.% Cr, 0.01-0.1 wt.% Zr, up to 0.15 wt.% impurities, and Al.

[0137] Example 22 is any of the preceding or subsequent exemplary metal products, wherein the aluminum alloy includes approximately 0.2-0.8 wt.% Cu, 0.3 wt.%-0.6 wt.% Fe, 1.4 wt.%-3.0 wt.% Mg, 0.2 wt.%-0.7 wt.% Mn, 0.2 wt.%-0.5 wt.% Si, 0.02 wt.%-0.1 wt.% Ti, 0.02 wt.%-3.0 wt.% Zn, 0.02 wt.%-0.1 wt.% Cr, 0.02 wt.%-0.05 wt.% Zr, and up to 0.15 wt.% impurities and Al.

[0138] Example 23 is any of the preceding or succeeding exemplary metal products, wherein the modified liquid metal contains at least 60% recycled aluminum.

[0139] Example 24 is any of the preceding or succeeding exemplary metal products, where the modified liquid metal contains at least 80% recycled aluminum.

[0140] Example 25 is any of the preceding or succeeding exemplary metal products, where the modified liquid metal contains less than or equal to 0.25 mL / 100 grams of hydrogen.

[0141] Example 26 is any of the preceding or succeeding exemplary metal products, including recycled aluminum, post-consumer beverage can scrap containing a mixture of recycled metals from can ends and can bodies.

[0142] Example 27 is a metal product of any of the preceding or subsequent examples, wherein the metal product includes a yield strength of at least 100 MPa.

[0143] Example 28 is any of the preceding or subsequent exemplary metal products, wherein the metal product includes an ultimate tensile strength of at least 210 MPa.

[0144] Example 29 is any preceding or succeeding exemplary metal product, wherein the metal product comprises a uniform elongation of at least 18%.

[0145] Example 30 is a preceding or subsequent exemplary metal product, wherein the metal product includes a total elongation of at least 20.5%.

[0146] Example 31 is a metal product of the preceding or subsequent examples, where the metal product includes an Fe-containing component.

[0147] Example 32 is a metal product of the preceding or following examples, in which the Fe-containing component has a length in the range of about 0.6 μm to about 1.8 μm.

[0148] Example 33 is any preceding or following exemplary metal product, where the metal product has a width-to-height ratio of about 3 or less.

[0149] The following examples serve to further illustrate the invention, but without limiting it. On the contrary, it should be clearly understood that after reading the description herein, resort can be made to various embodiments, modifications and equivalents that may suggest themselves to those skilled in the art without departing from the spirit of the invention. EXAMPLES

[0150] Example 1 Table 4 below shows the trace and alloying elements in UBC scrap, the first alternative alloy ("UBC1"), the second alternative alloy ("UBC2"), the standard 5754 direct chill cast aluminum alloy ("5754DC"), and two 5754 continuous cast aluminum alloys ("5754CC") and "5754CC1"). The 5754DC aluminum alloy, 5754CC aluminum alloy, and 5754CC1 aluminum alloy serve as comparative alloys, whereas the standard alloys were not prepared from mostly recycled scrap, e.g., UBC scrap. [Table 4]

[0151] The values ​​in Table 4 represent the approximate weight percentages of the particular elements. The UBC1 alloy is produced by adding about 0.25 wt% Cu and about 0.15 wt% Si to UBC scrap, resulting in a composition containing about 0.37 wt% Cu and about 0.29 wt% Si. The UBC2 alloy is made similarly to UBC1, but with the addition of about 1.0 wt% Mg, resulting in a composition containing about 2.59 wt% Mg. Comparing the 5754DC, 5754CC, and 5754CC1 alloys, they generally have less Fe, Si, and / or Cu compared to UBC scrap.

[0152] Example 2 6 is a chart 600 showing the longitudinal and transverse elongation, and strength properties of metal products prepared according to certain embodiments of the present disclosure. Chart 600 shows the longitudinal (referred to as "L" in FIG. 6) and transverse (referred to as "T" in FIG. 6) elongation, and strength properties of metal products formed from UBC1, UBC2, 5754DC, and 5754CC alloys from Table 4 above. As seen in Process 3 of FIG. 3, each metal product was hot rolled to an intermediate gauge and then cold rolled to a final gauge.

[0153] Chart 600 lists data for UBC1 alloy cast using the continuous casting apparatus disclosed herein, UBC2 alloy cast using the continuous casting apparatus disclosed herein, standard 5754DC aluminum alloy cast using direct chill casting in a vertical casting pit, and 5754CC aluminum alloy cast using a continuous casting apparatus. Both UBC1 and UBC2 alloys contain about 0.29-0.31 wt% Si, 0.37-0.39 wt% Cu, with UBC1 alloy containing about 1.5 wt% Mg and UBC2 alloy containing about 2.59 wt% Mg. The UBC1 and UBC2 samples were successfully cast using the continuous casting apparatus without cracks or other casting defects.

[0154] Additionally, chart 600 includes horizontal lines indicating various minimum specification limits, such as conventional 5754DC alloy. Yield strength specification limit 602 is about 100 MPa, uniform elongation specification limit 604 is about 18%, ultimate tensile strength specification limit 606 is about 210 MPa, and total elongation specification limit 608 is about 20.5%. Other minimum specification limits may also be used. In some cases, minimum specification limits within 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, 20%, or 30% of the specification limits may be used.

[0155] The standard 5754DC alloy achieved a longitudinal yield strength of about 116.00 MPa and a transverse yield strength of about 115.00 MPa, both above the yield strength specification limit 602, as well as a longitudinal ultimate tensile strength of about 245.5 MPa and a transverse ultimate tensile strength of about 235.9 MPa, both above the ultimate tensile strength specification limit 606. In addition, the standard 5754DC alloy achieved a longitudinal uniform elongation of about 21% and a transverse uniform elongation of about 22%, both above the uniform elongation specification limit 604, as well as a longitudinal total elongation of about 23% and a transverse total elongation of about 24%, both above the total elongation specification limit 608. These results are as would be expected for a standard 5754DC alloy prepared by conventional techniques using substantial amounts of primary aluminum (e.g., using mostly primary aluminum).

[0156] The continuously cast 5754CC alloy achieved a longitudinal yield strength of about 100.60 MPa and a transverse yield strength of about 115.95 MPa, one below and one above the yield strength specification limit 602, and a longitudinal ultimate tensile strength of about 204.3 MPa and a transverse ultimate tensile strength of about 233.5 MPa, one below and one above the ultimate tensile strength specification limit 606. In addition, the continuously cast 5754CC alloy achieved a longitudinal uniform elongation of about 19% and a transverse uniform elongation of about 14%, one above and one below the uniform elongation specification limit 604, and a longitudinal total elongation of about 22% and a transverse total elongation of about 15%, one above and one below the total elongation specification limit 608. These results indicate that even with 5754CC alloy, it is difficult to achieve the longitudinal and transverse specification limits with continuous casting.

[0157] The continuously cast UBC1 alloy achieved a longitudinal yield strength of about 88.18 MPa and a transverse yield strength of about 87.30 MPa, both below the yield strength specification limit 602, as well as a longitudinal ultimate tensile strength of about 207.1 MPa and a transverse ultimate tensile strength of about 203.4 MPa, both below the ultimate tensile strength specification limit 606. Additionally, the continuously cast UBC1 alloy achieved a longitudinal uniform elongation of about 19% and a transverse uniform elongation of about 17%, one above and one below the uniform elongation specification limit 604, as well as a longitudinal total elongation of about 23% and a transverse total elongation of about 18%, one above and one below the total elongation specification limit 608. These results show that with minimal or no additional magnesium added to the UBC scrap, it is difficult to achieve the specification limits, even if the casting is performed without substantial casting defects.

[0158] The continuously cast UBC2 alloy achieved a longitudinal yield strength of about 114.42 MPa and a transverse yield strength of about 115.95 MPa, both well above the yield strength specification limit 602, and a longitudinal ultimate tensile strength of about 241.8 MPa and a transverse ultimate tensile strength of about 234.5 MPa, both well above the ultimate tensile strength specification limit 606. Additionally, the continuously cast UBC2 alloy achieved a longitudinal uniform elongation of about 18% and a transverse uniform elongation of about 14%, both above the uniform elongation specification limit 604, as well as a longitudinal total elongation of about 21% and a transverse total elongation of about 15%, one above and one below the total elongation specification limit 608. These results indicate that the addition of magnesium to UBC scrap may allow specification limits to be achieved when the alloy is cast using continuous casting techniques.

[0159] Example 3 7-12 show various measurements obtained by testing three sets of metal products continuously cast using a UBC-based alloy with 1.5 wt. % Mg according to certain embodiments of the present disclosure, i.e., UBC1, identified in Table 4. Each set of metal products was prepared using the same continuous casting process (e.g., continuous casting system 402 in FIG. 4) and then rolled by cold rolling only (e.g., as seen in process 200 in FIG. 2), hot rolling only (e.g., as seen in process 100 in FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3). For ease of interpretation, the three rolling techniques may be identified as cold rolling only, hot rolling only, and hot and cold rolling. As used herein, the term "cold rolling only" may refer to cold rolling without any or a substantial amount of hot rolling, although other processing may occur. As used herein, the term "hot rolled only" can refer to hot rolling without any or substantial amounts of cold rolling, although other processing may occur. Tensile testing was performed according to ASTM B557 2" GL tensile testing.

[0160] Conventional rolling routes, including cold rolling and hot rolling, are generally complex and require substantial equipment and resources. Cold-only and hot-only routes may be desirable and more economical, using simpler and / or less equipment and resources. It may be desirable to prepare metal products by casting UBC-based alloys and performing hot rolling without cold rolling or cold rolling without hot rolling.

[0161] As can be seen in Figures 7-12, the continuously cast UBC1 alloy identified in Table 4 performed well in strength and formability after hot and cold rolling, but only performed moderately in strength and formability after hot rolling only or cold rolling only.

[0162] 7 is a chart 700 showing the yield strength of metal product samples continuously cast using UBC1. Chart 700 shows the longitudinal (L) and transverse (T) yield strengths in megapascals (MPa) for three metal product samples continuously cast using the UBC1 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0163] High yield strengths were observed for the cold rolled only samples, while intermediate yield strengths were observed for the hot rolled and hot and cold rolled samples.

[0164] 8 is a chart 800 showing the ultimate tensile strength of metal product samples continuously cast using UBC1. Chart 800 shows the ultimate tensile strength in megapascals (MPa) in the longitudinal (L) and transverse (T) directions for three metal product samples continuously cast using the UBC1 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0165] High ultimate tensile strengths were observed for the cold rolled only samples, while moderate ultimate tensile strengths were observed for the hot rolled and hot and cold rolled samples.

[0166] 9 is a chart 900 showing the uniform elongation of metal product samples continuously cast using UBC1. Chart 900 shows the longitudinal (L) and transverse (T) uniform elongation in percent elongation for three metal product samples continuously cast using the UBC1 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0167] High uniform elongation was observed in all three samples: cold rolled, hot rolled, and hot and cold rolled.

[0168] 10 is a chart 1000 showing the total elongation of metal product samples continuously cast using UBC1. Chart 1000 shows the total elongation in the longitudinal (L) and transverse (T) directions in percent elongation for three metal product samples continuously cast using the UBC1 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0169] High total elongation was observed in all three samples: cold rolled, hot rolled, and hot and cold rolled.

[0170] FIG. 11 is a chart 1100 showing three-point bend test results (inner bend angle β from the VDA 238-100 Tight Radius Bending Test (see FIG. 29)) of metal product samples continuously cast using UBC1. The samples tested in the three-point bend test were tested after a 10% pre-strain. Chart 1100 shows the longitudinal (L) and transverse (T) three-point bend test results in bend angles (°) of three metal product samples continuously cast using the UBC1 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0171] High bendability in the three-point bend test was observed for all three samples, the cold rolled sample, the hot rolled sample, and the hot and cold rolled sample, with the cold rolled sample exhibiting the largest internal bend angle (β angle) and the UBC-based aluminum alloys processed according to Process 100 of FIG. 1, Process 200 of FIG. 2, and Process 300 of FIG. 3 exhibiting the lowest bendability (i.e., formability). The hot rolled sample processed according to Process 100 of FIG. 1 exhibited the smallest internal bend angle (β angle) and the greatest bendability provided by the three process routes.

[0172] FIG. 12 is a chart 1200 showing plastic deformation test results of metal product samples continuously cast using UBC1. The results of the plastic deformation test are indicated by an R-value (e.g., Lankford modulus) equal to the true width strain divided by the true thickness strain. A higher R-value may be desirable, at least for the applications referred to herein, as it indicates greater resistance to thinning during elongation. The R-value may be calculated according to the "R10" test, where the R-value is determined at 10% strain. Chart 1200 shows the longitudinal (L) and transverse (T) R-values ​​of three metal product samples continuously cast using the UBC1 alloy identified in Table 4. Each sample underwent one of three different rolling techniques, including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 120 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0173] High R-values ​​in the plastic deformation tests were found mainly in the hot and cold rolled samples, with slightly lower R-values ​​in the hot rolled and cold rolled samples.

[0174] FIG. 13 shows a set of photomicrographs 1302, 1304, 1306 of metal product samples continuously cast using UBC1. Photomicrographs 1302, 1304, 1306 are photographs of metal samples made from the continuously cast UBC1 alloy of Table 4. Photomicrograph 1302 was taken from a metal product that was only cold rolled and annealed to the O temper and shows somewhat larger, elongated grains. Photomicrograph 1304 was taken from a metal product that was only hot rolled and annealed to the O temper and shows somewhat larger grains. Photomicrograph 1306 was taken from a metal product that was hot rolled, cold rolled, and annealed to the O temper and shows somewhat larger grains.

[0175] Example 4 Figures 14-19 show various measurements obtained by testing three sets of metal products continuously cast using a UBC-based alloy having 2.59 wt% Mg according to certain embodiments of the present disclosure. Each set of metal products was prepared similarly to those prepared with reference to Figures 7-13, but using the UBC2 alloy of Table 4. Tensile testing was performed according to ASTM B5513 2"GL tensile test.

[0176] As can be seen in Figures 14-19, the continuously cast UBC2 alloy performed nearly as well after being hot rolled only as it did when it was hot and cold rolled. Thus, UBC-based alloys with magnesium additions can be used to continuously cast metal products that achieve the desired performance after hot rolling without the need to cold roll the metal products.

[0177] 14 is a chart 1400 showing the yield strength of metal product samples continuously cast using a UBC-based alloy having 2.59 wt. % Mg according to certain embodiments of the present disclosure. Chart 1400 shows the longitudinal (L) and transverse (T) yield strengths in megapascals (MPa) for three metal product samples continuously cast using the UBC2 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0178] The cold rolled only sample exhibited a very high yield strength, while the hot rolled and hot and cold rolled samples exhibited more than sufficient yield strength. Interestingly, the hot rolled only sample achieved a yield strength substantially similar to the hot and cold rolled sample.

[0179] 15 is a chart 1500 showing the ultimate tensile strength of metal product samples continuously cast using a UBC-based alloy having 2.59 wt. % Mg according to certain embodiments of the present disclosure. Chart 1500 shows the ultimate tensile strength in megapascals (MPa) in the longitudinal (L) and transverse (T) directions for three metal product samples continuously cast using the UBC2 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0180] Very high ultimate tensile strengths were observed for the cold rolled only samples, while the hot rolled and hot and cold rolled samples exhibited more than adequate ultimate tensile strengths. Interestingly, the hot rolled only samples achieved substantially similar ultimate tensile strengths as the hot and cold rolled samples.

[0181] 16 is a chart 1600 showing the uniform elongation of metal product samples continuously cast using a UBC-based alloy having 2.59 wt. % Mg according to certain embodiments of the present disclosure. Chart 1600 shows the longitudinal (L) and transverse (T) uniform elongation in percent elongation for three metal product samples continuously cast using the UBC2 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0182] High uniform elongation was observed in all three samples: cold rolled, hot rolled, and hot and cold rolled. Interestingly, the sample that was only hot rolled achieved substantially the same uniform elongation as the hot and cold rolled sample.

[0183] 17 is a chart 1700 showing the total elongation of metal product samples continuously cast using a UBC-based alloy having 2.59 wt. % Mg according to certain embodiments of the present disclosure. Chart 1700 shows the total elongation in the longitudinal (L) and transverse (T) directions in percent elongation for three metal product samples continuously cast using the UBC2 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0184] High total elongation was observed in all three samples: cold rolled, hot rolled, and hot and cold rolled. Interestingly, the sample that was only hot rolled achieved a total elongation that was substantially similar to the hot and cold rolled sample.

[0185] FIG. 18 is a chart 1800 showing three-point bend test results (inner bend angle β) of metal product samples continuously cast using a UBC-based alloy with 2.59 wt.% Mg according to certain embodiments of the present disclosure. The samples tested in the three-point bend test were tested after a 10% pre-strain. Chart 1800 shows the longitudinal (L) and transverse (T) three-point bend test results in bend angles (°) of three metal product samples continuously cast using the UBC2 alloy identified in Table 4. Each sample underwent one of three different rolling techniques including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0186] The cold rolled only sample exhibited a very high internal bend angle (β angle) in the three-point bend test, while the hot rolled only sample and the hot and cold rolled samples exhibited lower internal bend angles (β angles) and were more than adequate in bendability. Interestingly, the hot rolled only sample achieved substantially similar bendability to the hot and cold rolled sample.

[0187] FIG. 19 is a chart 1900 showing plastic deformation testing of metal product samples continuously cast using a UBC-based alloy with 2.59 wt.% Mg according to certain embodiments of the present disclosure. The results of the plastic deformation testing are shown in an R-value, which is equal to the true width strain divided by the true thickness strain. A higher R-value may be desirable, at least for the applications mentioned herein, as it indicates a greater resistance to thinning during elongation. Chart 1900 shows the longitudinal (L) and transverse (T) R-values ​​of three metal product samples continuously cast using the UBC2 alloy identified in Table 4. Each sample underwent one of three different rolling techniques, including cold rolling (e.g., as seen in process 200 of FIG. 2), hot rolling (e.g., as seen in process 100 of FIG. 1), and a combination of cold and hot rolling (e.g., as seen in FIG. 3).

[0188] The cold rolled, hot rolled, and hot and cold rolled samples all exhibited high R-values ​​in the plastic deformation tests. Interestingly, the hot rolled only sample achieved substantially similar plastic deformation resistance as the hot and cold rolled sample.

[0189] FIG. 20 shows a series of photomicrographs 2002, 2004, 2006 of metal product samples continuously cast using a UBC based alloy having 2.59 wt. % Mg according to certain embodiments of the present disclosure. Photomicrographs 2002, 2004, 2006 are photographs of metal samples made from the continuously cast UBC2 alloy of Table 4. Photomicrograph 2002, which shows a metal product that has only been cold rolled and annealed to an O temper, shows smaller grains compared to at least photomicrograph 1302 of UBC1 as seen in FIG. 13, which has tensile characteristics of cold rolling. Photomicrograph 2004, which shows a metal product that has only been hot rolled and annealed to an O temper, shows smaller grains overall compared to at least photomicrograph 1304 of UBC1 as seen in FIG. 13. Micrograph 2006, showing the metal product that was hot rolled, cold rolled, and annealed to the O temper, showed generally smaller grains, at least as compared to micrograph 1306 of UBC1 as seen in FIG. 13. The grain structures of the hot rolled and hot and cold rolled samples, as seen in micrographs 2004 and 2006, respectively, are finer and may be more desirable than the grain structure of the cold rolled only sample shown in micrograph 2002. Interestingly, the hot rolled only sample achieved a substantially similar grain structure to the hot and cold rolled sample.

[0190] Small grain sizes may be desirable, at least for the applications described herein. The smaller grain size of metal products continuously cast from UBC-based alloys with the addition of further alloying elements (e.g., Mg) demonstrates how desirable metal products can be cast from UBC-based alloys with little or no additional primary aluminum.

[0191] Example 5 21 is a schematic diagram showing a series of different processes for continuous casting and rolling metal products according to certain embodiments of the present disclosure. Process line 1 at 2100 includes casting and hot rolling the metal product with coil cooling and cold rolling and without homogenization. Process line 2 at 2120 includes casting and hot rolling the metal product with quenching, homogenization, additional hot rolling, quenching, and cold rolling. Process line 3 at 2140 includes casting and hot rolling the metal product with quenching, homogenization, quenching, and cold rolling.

[0192] UBC-based alloys including UBC1 and UBC2, along with 5754CC1 (see Table 4), were prepared and processed according to process line 1 of 2100. Each alloy was further subjected to a continuous anneal ("CAL") by heating at a rate of 500°C / sec to a temperature of 520°C without soaking (i.e., the alloy was not held at this temperature). Figure 22 is a chart 2200 showing the mechanical properties of UBC1, UBC2, and 5754CC1 alloys. UBC1 achieved approximately 20% lower yield strength ("YS"), 15% lower ultimate tensile strength ("UTS"), 2% lower uniform elongation ("UE"), and similar total elongation ("TE") when compared to the 5754CC1 alloy. UBC2 achieved similar mechanical properties to the 5754CC1 alloy. FIG. 23 is a chart 2300 showing the texture component content of UBC1, UBC2, and 5754CC1 alloys, including Cube, Goss, Brass, S, and Copper ("Cu"). UBC1 exhibited lower texture component content as compared to the 5754CC1 alloy. UBC2 exhibited similar texture component content as the 5754CC1 alloy.

[0193] UBC-based alloys UBC1 and UBC2 (see Table 4) were prepared and processed according to 2100 Process Line 1, 2120 Process Line 2, and 2140 Process Line 3 (see FIG. 21). Additionally, the alloy samples were further subjected to batch annealing ("BA") or continuous annealing ("CAL") to provide the alloys in the O temper ("O"). Batch annealing was performed by heating the alloys at a rate of 50°C / hr to a temperature of 350°C and soaking for 2 hours. Continuous annealing was performed as described above. In further examples, after only continuous annealing, each alloy was further subjected to a paint bake ("PB") process. Paint bake was performed by applying a 2% strain to the alloys followed by heating the alloys to a temperature of 185°C and soaking for 20 minutes. FIG. 24 is a chart 2400 showing the yield strength of UBC1 and UBC2. FIG. 25 is a chart 2500 showing the ultimate tensile strength of UBC1 and UBC2. The alloys processed by 2100 process line 1 (see FIG. 21) showed high yield strength after batch annealing process. The higher strength is believed to be due to the energy stored in the alloy imparted by hot rolling and not relieved by homogenization. Furthermore, UBC1 showed 15-20% lower yield strength compared to UBC2, regardless of processing route, due to the lower Mg content of UBC1. The paint baking process increased the yield strength of both alloys by 45%-55%. FIG. 26 is a chart 2600 showing the uniform elongation of UBC1 and UBC2. FIG. 27 is a chart 2700 showing the total elongation of UBC1 and UBC2. UBC1 and UBC2 had lower elongation values ​​after processing by 2100 process line 1 (see FIG. 21) and batch annealing. The lower elongation is due to the energy stored in the alloys processed without homogenization. Additionally, the batch annealed alloys had lower elongation compared to the continuous annealed alloys due to the effect of heating rate on texture and grain size (slow heating rate for batch annealing vs. faster heating rate for continuous annealing). Figure 28 is a chart 2800 showing the three-point bend test results (outside bend angle α from the VDA 238-100 narrow radius bend test (see Figure 29)).UBC1 and UBC2 prepared according to 2100 process line 1 with batch annealing showed lower α angles than UBC1 and UBC2 prepared according to 2100 process line 1 with continuous annealing. The lower α angles are due to Fe-containing constituent particles in the alloys processed without homogenization. Furthermore, UBC2, which has a higher Mg content than UBC1, showed lower α angles than UBC1, regardless of the processing route.

[0194] UBC-based alloy UBC1 (see Table 4) was prepared and processed according to 2100 Process Line 1, 2120 Process Line 2, and 2140 Process Line 3 (see FIG. 21). The alloy was further subjected to batch annealing and continuous annealing to provide the alloy in the O temper. The batch annealing and continuous annealing steps were performed as described above. In some cases, the alloy processed by continuous annealing was also subjected to paint baking. The paint baking was performed as described above. FIG. 30 is a chart 3000 showing the yield strength of UBC1. FIG. 31 is a chart 3100 showing the ultimate tensile strength of UBC1. The yield strength and ultimate tensile strength were measured longitudinally ("0°") to the rolling direction of the alloy and transversely ("90°") to the rolling direction of the alloy. The UBC1 alloy prepared according to process line 1 of 2100 (see FIG. 21) had higher strength after batch annealing than after continuous annealing due to the energy stored in the alloy after hot rolling without homogenization. Similarly, UBC1 processed according to process line 2 of 2120 and process line 3 of 2140 (see FIG. 21) had 10% to 15% lower strength than UBC1 prepared by process line 1 of 2100 (see FIG. 21). Furthermore, the use of a paint baking process increased the yield strength regardless of the processing route. FIG. 32 is a chart 3200 showing the uniform elongation of UBC1. FIG. 33 is a chart 3300 showing the total elongation of UBC1. The uniform elongation and total elongation were measured longitudinally ("0°") to the rolling direction of the alloy and transversely ("90°") to the rolling direction of the alloy. The UBC1 alloy processed according to process line 1 of 2100 (see FIG. 21) had lower elongation after batch annealing compared to the alloy processed by continuous annealing due to the energy stored in the alloy without homogenization after hot rolling. Similarly, the UBC1 alloy processed according to process line 2 of 2120 and process line 3 of 2140 (see FIG. 21) showed 5% to 8% higher elongation than the UBC1 alloy processed according to process line 1 of 2100 (see FIG. 21). FIG. 34 is a chart 3400 showing three-point bend test results (outer bend angle α according to VDA238-100 narrow radius bend test (see FIG. 29)).UBC1 processed by process line 1 at 2100 with batch annealing exhibited a lower α angle than UBC1 processed according to process line 2 at 2120 and process line 3 at 2140 (see FIG. 21). The lower α angle is attributed to the Fe-containing component particles in the alloy processed without homogenization. Furthermore, applying a 10% partial strain ("PS", referred to as "10%" in FIG. 34) to UBC1 resulted in a 30% to 40% lower α angle, regardless of the processing route.

[0195] UBC-based alloy UBC2 (see Table 4) was prepared and processed according to 2100 Process Line 1, 2120 Process Line 2, and 2140 Process Line 3 (see FIG. 21). Additionally, the alloy samples were further subjected to batch annealing or continuous annealing to provide the alloy in the O temper ("O"). Batch annealing and continuous annealing were performed as described above. In some cases, the alloy processed by continuous annealing was further subjected to paint baking. Paint baking was performed as described above. FIG. 35 is a chart 3500 showing the yield strength of UBC2. FIG. 36 is a chart 3600 showing the ultimate tensile strength of UBC2. The yield strength and ultimate tensile strength were measured longitudinally ("0°") to the rolling direction of the alloy and transversely ("90°") to the rolling direction of the alloy. UBC2 alloy processed according to 2100 process line 1 (see FIG. 21) had higher strength after batch annealing than after continuous annealing due to the energy stored in the alloy after hot rolling without homogenization. Similarly, UBC2 processed according to 2120 process line 2 and 2140 process line 3 (see FIG. 21) had 10% to 15% less strength than UBC2 processed according to 2100 process line 1 (see FIG. 21). Furthermore, the use of a paint baking process increased the yield strength regardless of the processing route. FIG. 37 is a chart 3700 showing the uniform elongation of UBC2. FIG. 38 is a chart 3800 showing the total elongation of UBC2. The uniform and total elongation were measured longitudinally ("0°") to the rolling direction of the alloy and transversely ("90°") to the rolling direction of the alloy. The UBC2 alloy processed according to 2100 process line 1 (see FIG. 21) had lower elongation after batch annealing than after continuous annealing due to the energy stored in the alloy after hot rolling without homogenization. Similarly, UBC2 processed according to 2120 process line 2 and 2140 process line 3 (see FIG. 21) showed 5% to 8% higher elongation than UBC2 processed by 2100 process line 1 (see FIG. 21). FIG. 39 is a chart 3900 showing three-point bend test results (outer bend angle α from VDA238-100 narrow radius bend test (see FIG. 29)).UBC2 processed according to 2100 process line 1 with batch annealing exhibited a lower outer bend angle (α angle) than UBC2 processed according to 2100 process line 1 with continuous annealing due to differences in heat rates that affect the grain structure and texture of the material. Furthermore, applying a 10% partial strain ("PS", referred to as "10%" in FIG. 39) to UBC2 resulted in a 35% to 45% lower outer bend angle (α angle), regardless of the processing route.

[0196] UBC-based alloy UBC1 was prepared and processed according to 2100 process line 1, 2120 process line 2, and 2140 process line 3 (see FIG. 21). The alloy was further subjected to batch annealing and continuous annealing as described above. FIG. 40 shows micrographs illustrating the fine particle content of the alloy after various processing routes using batch annealing. Micrograph 4002 shows the fine particle content of UBC1 processed according to 2100 process line 1, micrograph 4004 shows the fine particle content of UBC1 after processing according to 2120 process line 2, and micrograph 4006 shows the fine particle content of UBC1 after processing according to 2140 process line 3. In general, the UBC1 alloy processed according to 2100 process line 1 provided a higher amount of precipitates and iron-containing elements than the UBC1 alloy processed according to 2120 process line 2 and 2140 process line 3.

[0197] Figure 41 shows micrographs showing the fine particle content of the alloys after various processing routes using continuous annealing. Micrograph 4102 shows the fine particle content of UBC1 processed according to process line 1 of 2100, micrograph 4104 shows the fine particle content of UBC1 after processing according to process line 2 of 2120, and micrograph 4106 shows the fine particle content of UBC1 after processing according to process line 3 of 2140. UBC1 processed with continuous annealing showed less fine particle than UBC1 processed with batch annealing.

[0198] UBC-based alloy UBC2 was prepared and processed according to 2100 process line 1, 2120 process line 2, and 2140 process line 3 (see FIG. 21). The alloys were further subjected to batch or continuous annealing as described above. FIG. 42 shows micrographs illustrating the fine particle content of the alloys after various processing routes using batch annealing. Micrograph 4202 shows the fine particle content of UBC2 processed according to 2100 process line 1, micrograph 4204 shows the fine particle content of UBC2 after processing according to 2120 process line 2, and micrograph 4206 shows the fine particle content of UBC2 after processing according to 2140 process line 3. In general, UBC2 processed according to 2100 process line 1 provided a higher amount of precipitates and iron-containing components than UBC2 processed according to 2120 process line 2 and 2140 process line 3.

[0199] Figure 43 shows micrographs showing the fine particle content of the alloys after various processing routes using continuous annealing. Micrograph 4302 shows the fine particle content of UBC2 processed according to process line 1 of 2100, micrograph 4304 shows the fine particle content of UBC2 after processing according to process line 2 of 2120, and micrograph 4306 shows the fine particle content of UBC2 after processing according to process line 3 of 2140. UBC2 processed with continuous annealing showed less fine particle than UBC2 processed with batch annealing.

[0200] UBC-based alloy UBC1 was prepared and processed according to 2100 process line 1, 2120 process line 2, and 2140 process line 3 (see FIG. 21). The alloys were further subjected to batch or continuous annealing as described above. FIG. 44 shows micrographs illustrating the grain morphology of the alloys after various processing routes with batch annealing. Micrograph 4402 shows the grain morphology of UBC1 processed according to 2100 process line 1, micrograph 4404 shows the grain morphology of UBC1 after processing according to 2120 process line 2, and micrograph 4406 shows the grain morphology of UBC1 after processing according to 2140 process line 3. In general, UBC1 processed according to 2100 process line 1 with batch annealing provided a greater amount of unrecrystallized grains than those processed according to 2120 process line 2 with batch annealing and 2140 process line 3 with batch annealing.

[0201] FIG. 45 shows micrographs showing the fine grain content of the alloys after various processing routes using continuous annealing. Micrograph 4502 shows the grain morphology of UBC1 processed according to process line 1 of 2100, micrograph 4504 shows the grain morphology of UBC1 after processing according to process line 2 of 2120, and micrograph 4506 shows the grain morphology of UBC1 after processing according to process line 3 of 2140. The UBC1 alloy processed with continuous annealing exhibited small and fine recrystallized grains in contrast to the grain structure of the UBC1 alloy processed with batch annealing, which exhibited coarse and elongated grains. The difference in grain structure is due to the heating rate and heat treatment temperature.

[0202] UBC-based alloy UBC2 was prepared and processed according to 2100 process line 1, 2120 process line 2, and 2140 process line 3 (see FIG. 21). The alloys were further subjected to batch or continuous annealing as described above. FIG. 46 shows micrographs illustrating the grain morphology of the alloys after various processing routes with batch annealing. Micrograph 4602 shows the grain morphology of UBC2 processed according to 2100 process line 1, micrograph 4604 shows the grain morphology of UBC2 after processing according to 2120 process line 2, and micrograph 4606 shows the grain morphology of UBC2 after processing according to 2140 process line 3. In general, UBC2 processed according to 2100 process line 1 with batch annealing provided a greater amount of unrecrystallized grains than those processed according to 2120 process line 2 with batch annealing and 2140 process line 3 with batch annealing.

[0203] FIG. 47 shows micrographs showing the grain morphology of the alloys after various processing routes using continuous annealing. Micrograph 4702 shows the grain morphology of UBC2 processed according to process line 1 of 2100, micrograph 4704 shows the grain morphology of UBC2 after processing according to process line 2 of 2120, and micrograph 4706 shows the grain morphology of UBC2 after processing according to process line 3 of 2140. UBC2 processed with continuous annealing exhibited fine and small recrystallized grain structure, while UBC2 processed with batch annealing (FIG. 46) resulted in relatively coarse grains with some elongated grains. The difference in grain structure can be attributed to the heating rate and heat treatment temperature.

[0204] UBC-based alloys UBC1 and UBC2 were prepared and processed according to process line 1 of 2100, process line 2 of 2120, and process line 3 of 2140 (see FIG. 21), all batch annealed as described above. FIG. 48 is a chart 4800 showing the texture component content of the alloys after processing with batch annealing, e.g., cube, goss, brass, S, and copper ("Cu") content. Additionally, alloys were prepared and processed according to process line 1 of 2100, process line 2 of 2120, and process line 3 of 2140, all continuous annealed as described above. FIG. 49 is a chart 4900 showing the texture component content of the alloys after processing with continuous annealing, e.g., cube, goss, brass, S, and copper ("Cu") content. The alloys processed by batch annealing showed more rolling texture components (e.g., Brass, S, and Cu) compared to the alloys processed by continuous annealing. However, the alloys processed by continuous annealing showed a more random and uniform texture, regardless of the processing route and subsequent heat treatment.

[0205] FIG. 50 is a chart 5000 showing a comparison of the texture components cube, brass, and Cu in UBC1 and UBC2 alloys processed according to 2100 process line 1, 2120 process line 2, and 2140 process line 3 (see FIG. 21) with batch annealing or continuous annealing. The alloys processed with batch annealing exhibited more rolling texture (e.g., brass and Cu) compared to the alloys processed with continuous annealing. The alloys processed with continuous annealing exhibited more random and uniform texture.

[0206] 51 shows scanning electron microscope (SEM) micrographs of UBC1 processed as above by continuous annealing (CAL). Micrograph 5102 shows precipitate formation in UBC1 after processing by process line 1 of 2100, micrograph 5104 shows precipitate formation in UBC1 after processing by process line 2 of 2120, and micrograph 5106 shows precipitate formation in UBC1 after processing by process line 3 of 2140.

[0207] FIG. 52 depicts SEM micrographs of UBC2 processed by 2100 process line 1 with continuous annealing (micrograph 5202), 2120 process line 2 with continuous annealing (micrograph 5204), and 2140 process line 3 with continuous annealing (micrograph 5206). For both alloys, 2100 process line 1 provided undissolved precipitates due to lack of homogenization after hot rolling. No significant differences in Fe content were observed for UBC1 or UBC2 processed by 2120 process line 2 or 2140 process line 3.

[0208] Scanning electron microscopy was used for further analysis of the precipitated particles found in UBC1 and UBC2. FIG. 53 is a chart 5300 showing particle size distribution in the alloys after processing according to 2100 process line 1, 2120 process line 2, and 2140 process line 3. FIG. 54 is a chart 5400 showing particle aspect ratio in the alloys after processing according to 2100 process line 1, 2120 process line 2, and 2140 process line 3. Both alloys processed according to 2100 process line 1 exhibited 20% to 40% longer Fe-containing constituent particles (see FIG. 53) and 15% to 20% higher aspect ratios for the Fe-containing constituent particles (see FIG. 54) than the alloys processed according to 2120 process line 2 and 2140 process line 3. The difference in the alloy processed according to 2100 process line 1 may be due to a lack of homogenization.

[0209] Along with 5754CC1, UBC-based alloys UBC1 and UBC2 were prepared and processed according to process line 1 of 2100 with continuous annealing (CAL) as described above. From the stress-strain curves of UBC1 (see FIG. 55), UBC2 (see FIG. 56), and 5754CC1 (see FIG. 57), it can be seen that all alloys exhibited similar Luder bands 5502 (see FIG. 55), 5602 (see FIG. 56), 5702 (see FIG. 57) before the onset of uniform deformation. UBC1 exhibited a slight yield point elongation (see FIG. 55) compared to 5754CC1 (see FIG. 57). Conversely, UBC2 exhibited a similar yield point elongation (see FIG. 56) to 5754CC1 (see FIG. 57) as indicated by the similar onset of uniform deformation at about 0.3%-0.4% true strain.

[0210] All patents, publications, and abstracts cited above are incorporated herein by reference in their entirety. Various embodiments of the invention have been described to accomplish various objects of the invention. It should be recognized that these embodiments are merely illustrative of the principles of the invention. Many modifications and adaptations thereof will be readily apparent to those skilled in the art without departing from the spirit and scope of the invention as defined in the following claims. Some of the embodiments of the present disclosure are described in [Item 1] to [Item 33] below. [Item 1] Melting the recycled aluminum into liquid metal; adding an alloying element to the liquid metal to form a modified liquid metal, the alloying element comprising magnesium, silicon, or copper; casting the modified liquid metal into a metal product, the modified liquid metal comprising at least 50% recycled aluminum; and and rolling said metal product. [Item 2] 2. The method of claim 1, wherein the rolling comprises hot rolling the metal product to a gauge for delivery. [Item 3] 3. The method according to claim 2, wherein the gauge for delivery is an intermediate gauge. [Item 4] 3. The method according to claim 2, wherein the gauge for delivery is a final gauge. [Item 5] 2. The method of claim 1, wherein the rolling comprises cold rolling the metal product to a gauge for delivery. [Item 6] 6. The method of claim 5, wherein the gauge for delivery is an intermediate gauge. [Item 7] 6. The method of claim 5, wherein the gauge for delivery is a final gauge. [Item 8] 2. The method of claim 1, wherein the rolling comprises hot rolling and cold rolling the metal product. [Item 9] 9. The method according to any one of items 1 to 8, wherein the modified liquid metal comprises magnesium in an amount up to about 7 wt.%. [Item 10] 9. The method according to any one of items 1 to 8, wherein the modified liquid metal comprises magnesium in an amount of at least 1.5 wt.%. [Item 11] 9. The method according to any one of items 1 to 8, wherein the modified liquid metal comprises magnesium in an amount of about 1.5% by weight to about 4% by weight. [Item 12] 12. The method according to any one of the preceding claims, further comprising reheating the metal product after the rolling to an annealing temperature, the annealing temperature being below a solidus temperature of the metal product. [Item 13] 13. The method of any one of items 1 to 12, wherein the casting comprises continuously casting the modified liquid metal. [Item 14] 13. The method of any one of items 1 to 12, wherein the casting comprises direct chill casting of the modified liquid metal. [Item 15] 15. The method according to any one of items 1 to 14, wherein the recycled aluminum comprises used beverage can scrap containing a mixture of recycled metals from can ends and can bodies. [Item 16] 16. The method according to any one of items 1 to 15, wherein the modified liquid metal comprises at least 60% recycled aluminum. [Item 17] 17. The method of claim 16, wherein the modified liquid metal comprises at least 80% recycled aluminum. [Item 18] 18. The method according to any one of items 1 to 17, wherein the modified liquid metal comprises a hydrogen content of 0.25 mL / 100 grams or less. [Item 19] 19. A metal product cast from recycled materials by the method according to any one of items 1 to 18. [Item 20] 1. A metal product comprising an aluminum alloy comprising approximately 0.01% to 1.0% by weight Cu, 0.15% to 0.8% by weight Fe, 0.5% to 7.0% by weight Mg, 0.01% to 1.2% by weight Mn, up to 1.5% by weight Si, up to 0.15% by weight impurities, and Al, A metal product, wherein the metal product is cast from a modified liquid metal containing at least 50% recycled aluminum. [Item 21] 21. The metal product according to item 20, wherein the aluminum alloy comprises about 0.1-0.9 wt.% Cu, 0.25 wt.%-0.7 wt.% Fe, 1.0 wt.%-5.0 wt.% Mg, 0.1 wt.%-0.9 wt.% Mn, 0.01 wt.%-1.0 wt.% Si, 0.01 wt.%-0.15 wt.% Ti, 0.01 wt.%-5.0 wt.% Zn, 0.01 wt.%-0.25 wt.% Cr, 0.01 wt.%-0.1 wt.% Zr, impurities up to 0.15 wt.%, and Al. [Item 22] 21. The metal product according to item 20, wherein the aluminum alloy comprises about 0.2-0.8 wt.% Cu, 0.3 wt.%-0.6 wt.% Fe, 1.4 wt.%-3.0 wt.% Mg, 0.2 wt.%-0.7 wt.% Mn, 0.2 wt.%-0.5 wt.% Si, 0.02 wt.%-0.1 wt.% Ti, 0.02 wt.%-3.0 wt.% Zn, 0.02 wt.%-0.1 wt.% Cr, 0.02 wt.%-0.05 wt.% Zr, impurities up to 0.15 wt.%, and Al. [Item 23] 23. The metal product according to any one of items 20 to 22, wherein the modified liquid metal comprises at least 60% of the recycled aluminum. [Item 24] 24. The metal product according to any one of items 20 to 23, wherein the modified liquid metal comprises at least 80% of the recycled aluminum. [Item 25] 25. The metal product according to any one of claims 20 to 24, wherein the modified liquid metal comprises a hydrogen content of 0.25 mL / 100 grams or less. [Item 26] 26. The metal product of any one of items 20 to 25, wherein the recycled aluminum comprises used beverage can scrap containing a mixture of recycled metals from can ends and can bodies. [Item 27] 27. The metal product according to any one of claims 20 to 26, wherein the metal product has a yield strength of at least 100 MPa. [Item 28] 28. The metal product according to any one of claims 20 to 27, wherein the metal product has an ultimate tensile strength of at least 210 MPa. [Item 29] 29. The metal product according to any one of claims 20 to 28, wherein the metal product has a uniform elongation of at least 18%. [Item 30] 30. The metal product according to any one of claims 20 to 29, wherein the metal product has a total elongation of at least 20.5%. [Item 31] 31. The metal product according to any one of items 20 to 30, wherein the metal product comprises an Fe-containing component. [Item 32] Item 32. The metal product according to item 31, wherein the Fe-containing component has a length in the range of about 0.6 μm to about 1.8 μm. [Item 33] 33. The metal product of any one of claims 20 to 32, wherein the metal product comprises intermetallic particles having a width-to-height ratio of about 3 or less.

Claims

1. 1. A metal product comprising an aluminum alloy having an elemental composition comprising 0.1 wt.% to 0.9 wt.% Cu, 0.25 wt.% to 0.7 wt.% Fe, 0.6 wt.% to 5.0 wt.% Mg, 0.1 wt.% to 0.9 wt.% Mn, 0.01 wt.% to 1.0 wt.% Si, 0.01 wt.% to 0.15 wt.% Ti, 0.01 wt.% to 5.0 wt.% Zn, 0.01 wt.% to 0.09 wt.% Cr, 0.01 wt.% to 0.1 wt.% Zr, and up to 0.15 wt.% impurities, balance Al, comprising an Fe-containing component, The impurities include at least one selected from Sn, Ga, Ca, Bi, Na, Pb, Li, W, Mo, Ni, and V, each of which is present in an amount of 0.05% by weight or less; metal products.

2. 2. The metal product of claim 1, wherein the aluminum alloy has an elemental composition including approximately 0.2-0.8 wt.% Cu, 0.3-0.6 wt.% Fe, 1.4-3.0 wt.% Mg, 0.2-0.7 wt.% Mn, 0.2-0.5 wt.% Si, 0.02-0.1 wt.% Ti, 0.02-3.0 wt.% Zn, 0.02-0.09 wt.% Cr, 0.02-0.05 wt.% Zr, and up to 0.15 wt.% impurities, balance Al.

3. 3. The metal product of claim 1 or 2, wherein the metal product comprises a yield strength of at least 100 MPa.

4. The metal product of any one of claims 1 to 3, wherein the metal product has an ultimate tensile strength of at least 210 MPa.

5. The metal product of any one of claims 1 to 4, wherein the metal product has a uniform elongation of at least 18%.

6. The metal product of any one of claims 1 to 5, wherein the metal product has a total elongation of at least 20.5%.

7. The metal product of any one of claims 1 to 6, wherein the Fe-containing component has a length in the range of about 0.6 μm to about 1.8 μm.

8. The metal product of any one of claims 1 to 7, wherein the metal product comprises intermetallic particles having a width-to-height ratio of about 3 or less.

Citation Information

Patent Citations

  • High-strength aluminum alloy plate for press forming and production thereof

    JP1992131347A

  • Aluminum-magnesium alloy for welded structure having improved mechanical property

    JP1997111386A

  • Al-mg-si series al alloy sheet excellent in toughness and bendability

    JP2001262264A

  • Aluminum alloy sheet excellent in coating / Baking hardenability and workability and its production method

    JP2001329328A

  • Aluminum alloy forging and method for manufacturing same

    JP2011214093A